Laminated sheet
Patent Information
- Application Number
- JP2024211908
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-05-19
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-05-18
AI Technical Summary
【0013】 本発明によれば、高い透明性を有し、かつ着色が抑制された積層シートを得ることができる。
Smart Images

Figure 2025032206000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated sheet. [Background technology]
[0002] In recent years, materials using renewable natural fibers have been attracting attention due to the need to replace petroleum resources and growing environmental awareness. Among natural fibers, fibrous cellulose with a fiber diameter of 10 μm to 50 μm, especially fibrous cellulose (pulp) derived from wood, has been widely used mainly for paper products.
[0003] As for fibrous cellulose, fine fibrous cellulose with a fiber diameter of 1 μm or less is also known. Fine fibrous cellulose is attracting attention as a new material and has a wide range of uses. For example, development of sheets, resin composites, and thickeners containing fine fibrous cellulose is underway.
[0004] For example, Patent Document 1 discloses a method for producing fine fibers, which includes the steps of (a) introducing a substituent having electrostatic and / or steric functionality into a fine fiber raw material to obtain a substituted fiber, (b) mechanically treating the substituted fiber, and (c) eliminating a part or all of the introduced substituents from the substituted fine fibers obtained in step (b) to obtain a substituted-free fine fiber. Patent Document 2 discloses a method for producing a deesterified compound, which includes a step of heating a compound having an ester derived from phosphoric acid and / or an ester derived from carboxylic acid in the presence of a nitrogen-containing compound exhibiting basicity. These documents discuss eliminating the substituents introduced into the fine fibers.
[0005] Patent Document 3 discloses a method for producing a fine fiber-containing sheet, which comprises at least the steps of (a) introducing a substituent having electrostatic and / or three-dimensional functionality into a fiber raw material to obtain a substituted fiber, (b) mechanically treating the substituted fiber obtained in step (a) to obtain a substituted fine fiber, (c) preparing a sheet from the substituted fine fiber obtained in step (b), and (d) eliminating at least a part of the introduced substituent from the sheet obtained in step (c). Here, a method for eliminating the substituent after forming a sheet from the substituted fine fiber is considered.
[0006] Furthermore, Patent Documents 4 and 5 disclose a method for producing cellulose xanthate nanofibers by defibrating cellulose xanthate or a cationic substituted cellulose xanthate. Patent Document 4 also examines a method for returning cellulose xanthate nanofibers to unmodified cellulose by regenerating the nanofibers as necessary. Patent Document 5 discloses a sheet containing cellulose fine fibers from which functional groups have been removed from cellulose derivative fine fibers, and which has an average fiber diameter of 3 nm to 300 nm.
[0007] Meanwhile, in recent years, the development of a composite containing a fine fibrous cellulose-containing sheet and a resin layer has also been promoted. In such a composite, for example, studies have been made to improve the adhesion between the fine fibrous cellulose-containing sheet (fiber layer) and the resin layer. For example, Patent Document 6 discloses a laminate having a fiber layer containing fine fibrous cellulose and a resin layer in contact with one side of the fiber layer. Patent Document 7 discloses a laminate having a fiber layer formed of fine fibrous cellulose, a resin layer, and an adhesive layer provided between the fiber layer and the resin layer, and Patent Document 8 discloses a laminate having a substrate, an anchor layer, and a cellulose nanofiber layer provided in this order. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] International Publication No. 2013 / 176049 [Patent Document 2] JP 2015-098526 A [Patent Document 3] International Publication No. 2015 / 182438 [Patent Document 4] International Publication No. 2017 / 111103 [Patent Document 5] JP 2019-7101 A [Patent Document 6] International Publication No. 2017 / 126432 [Patent Document 7] JP 2017-056715 A [Patent Document 8] JP 2014-079938 A Summary of the Invention [Problem to be solved by the invention]
[0009] In the course of conducting research into a laminated sheet having a sheet (fiber layer) containing fine fibrous cellulose and a resin layer, the inventors discovered that such a laminated sheet may suffer from reduced transparency or discoloration.
[0010] Therefore, in order to solve such problems of the conventional technology, the present inventors have conducted research with the aim of providing a laminate sheet having a fiber layer containing fine fibrous cellulose and a resin layer, which has high transparency and suppressed coloration. [Means for solving the problem]
[0011] As a result of intensive research to solve the above problems, the inventors have found that in a laminate sheet having a fiber layer and a resin layer disposed on at least one side of the fiber layer, by containing fibrous cellulose having an introduction amount of a substituent of less than 0.5 mmol / g in the fiber layer and a fiber width of 1 to 10 nm, a laminate sheet having high transparency and suppressed coloration can be obtained. Specifically, the present invention has the following configuration.
[0012] [1] A laminated sheet having a fiber layer and a resin layer disposed on at least one surface of the fiber layer, The fiber layer is a laminated sheet comprising fibrous cellulose having an introduction amount of a substituent of less than 0.5 mmol / g and a fiber width of 1 to 10 nm. [2] The laminate sheet according to [1], wherein the substituent is an anionic group. [3] The laminate sheet according to [2], wherein the anionic group is a phosphorus oxo acid group or a functional group derived from a phosphorus oxo acid group. [4] The laminate sheet according to any one of [1] to [3], wherein the fibrous cellulose has a carbamide group. [5] The laminate sheet according to any one of [1] to [4], wherein the fiber layer has a thickness of 20 μm or more. [6] The density of the fibre layer is 1.0 g / cm 3 The laminate sheet according to any one of [1] to [5] above. [7] The laminate sheet according to any one of [1] to [6], wherein the resin layer is directly laminated on the fiber layer. [8] The laminate sheet according to any one of [1] to [7], wherein the resin layer contains at least one resin selected from a polycarbonate resin and an acrylic resin. [9] The laminate sheet according to any one of [1] to [8], wherein the resin layer further contains an adhesion assistant.
[10] The laminate sheet according to [9], wherein the adhesion assistant is at least one selected from an isocyanate compound and an organosilicon compound.
[11] The laminate sheet according to [9] or
[10] , wherein the adhesion aid is an isocyanate compound, and the content of the isocyanate compound is 10 parts by mass or more and 40 parts by mass or less per 100 parts by mass of the resin contained in the resin layer.
[12] The laminate sheet according to any one of [1] to
[11] , having a YI value of 2.0 or less.
[13] The laminate sheet according to any one of [1] to
[12] , having a haze of 2.0% or less.
[14] The laminate sheet according to any one of [1] to
[13] , which is for use as an optical member.
[15] A laminate comprising the laminate sheet according to any one of [1] to
[14] and an adherend. Effect of the Invention
[0013] According to the present invention, a laminate sheet having high transparency and suppressed coloration can be obtained. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is a cross-sectional view illustrating the configuration of the laminate sheet of the present invention. [Diagram 2] FIG. 2 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fibrous cellulose having phosphorus oxoacid groups and pH. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will be described in detail below. The following description of the constituent elements may be based on representative embodiments or specific examples, but the present invention is not limited to such embodiments. In this specification, a numerical range expressed using "~" means a range including the numerical values before and after "~" as the lower and upper limits.
[0016] (Laminated sheet) The present invention relates to a laminate sheet having a fiber layer and a resin layer disposed on at least one surface of the fiber layer, wherein the fiber layer contains fibrous cellulose having an introduction amount of a substituent of less than 0.5 mmol / g and a fiber width of 1 to 10 nm.
[0017] FIG. 1 is a cross-sectional view illustrating the configuration of the laminate sheet of the present invention. As shown in FIG. 1, the laminate sheet 10 of the present invention has a resin layer 2 and a fiber layer 6. The resin layer 2 is directly laminated on the fiber layer 6, and the resin layer 2 and the fiber layer 6 are in contact with each other on one side. The laminate sheet 10 of the present invention may have at least one resin layer 2 and one fiber layer 6, but may have two or more resin layers 2 or two or more fiber layers 6. For example, the laminate sheet may have a configuration in which a fiber layer, a resin layer, and a fiber layer are laminated in this order, or a configuration in which a resin layer, a fiber layer, and a resin layer are laminated in this order.
[0018] In the past, in order to obtain a highly transparent sheet, it was considered to increase the amount of substituents introduced into the fine fibrous cellulose, thereby obtaining a fine fibrous cellulose with a small fiber width. However, when fine fibrous cellulose with a high amount of substituents is blended into a sheet, the sheet tends to become discolored when heated in the sheet manufacturing process or in the usage environment. On the other hand, when the amount of substituents introduced is controlled to be low by controlling the substituent introduction process, the fine fibrous cellulose is not sufficiently defibrated, making it difficult to obtain a highly transparent sheet. Therefore, the present inventors have repeatedly studied the manufacturing process of fine fibrous cellulose, and have succeeded in finely reducing the fiber width to a level of 1 to 10 nm, despite the low amount of substituents introduced, such as less than 0.5 mmol / g. And, it was found that a sheet blended with fibrous cellulose with a low amount of substituents and a fiber width finely reduced to a level of 1 to 10 nm is highly transparent and coloring is suppressed. When such a fine fibrous cellulose-containing sheet is laminated on a resin layer, the transparency of the resin layer is maintained without being impaired.
[0019] The total light transmittance of the laminate sheet is preferably 88% or more, more preferably 90% or more, even more preferably 91% or more, and particularly preferably 91.5% or more. By setting the total light transmittance of the laminate sheet within the above range, the laminate sheet of the present invention can be applied to applications where transparent glass has been used in the past. Here, the total light transmittance is a value measured using a haze meter (Murakami Color Research Laboratory, HM-150) in accordance with JIS K 7361-1:1997.
[0020] The haze of the laminate sheet is preferably 2.0% or less, more preferably 1.5% or less, and even more preferably 1.0% or less. The lower limit of the haze of the laminate sheet is not particularly limited, and may be 0%. Here, the haze is a value measured using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory Co., Ltd.) in accordance with JIS K 7136:2000.
[0021] In the laminated sheet of the present invention, the interlayer adhesion between the fiber layer and the resin layer is also excellent. 2 When 100 cross-cuts of the above are inserted, cellophane tape (manufactured by Nichiban Co., Ltd.) is attached and pressed on them, and then peeled in a 90° direction, the number of squares where the fiber layer has peeled off from the resin layer is less than 5 points. In such a case, it can be determined that the interlayer adhesion between the fiber layer and the resin layer is good. The number of peeled squares is more preferably 3 points or less, even more preferably 1 point or less, and particularly preferably 0 points.
[0022] The laminate sheet of the present invention has a fiber layer and a resin layer, and the fiber layer can also function as a layer for reinforcing the resin layer. This increases the strength of the laminate sheet itself. In addition, even when the laminate sheet is attached to an adherend such as another resin film or resin plate, the fiber layer functions as a layer for reinforcing the adherend. For example, by using a resin plate such as a polycarbonate plate as the adherend and attaching the laminate sheet to this resin plate, the mechanical strength of the resin plate can be reinforced. In this way, the laminate sheet having a fiber layer also has the effect of reinforcing the adherend.
[0023] The reinforcing effect when the laminate sheet is attached to the adherend can be evaluated as excellent when the flexural modulus after the laminate sheet is attached to the adherend is 1.5 times or more compared to the flexural modulus of the adherend. It is particularly preferable that the flexural modulus after the laminate sheet is attached to the adherend is 2.0 times or more compared to the flexural modulus of the adherend. When attaching the adherend to the laminate sheet, the adherend and the laminate sheet are overlapped and then hot pressed to a temperature equal to or higher than the glass transition temperature of the adherend to produce the laminate sheet.
[0024] The laminate sheet of the present invention has excellent mechanical strength by itself. For example, the tensile modulus of the laminate sheet at 23°C and a relative humidity of 50% is preferably 2.5 GPa or more, more preferably 5.0 GPa or more, and even more preferably 10 GPa or more. The tensile modulus of the laminate sheet at 23°C and a relative humidity of 50% is preferably 30 GPa or less, more preferably 25 GPa or less, and even more preferably 20 GPa or less. The tensile modulus of the laminate sheet is a value measured in accordance with JIS P 8113.
[0025] The total thickness of the laminate sheet is not particularly limited, but is preferably 30 μm or more, more preferably 40 μm or more, even more preferably 50 μm or more, even more preferably 60 μm or more, and particularly preferably 70 μm or more. The total thickness of the laminate sheet is preferably 1000 μm or less. The thickness of the laminate sheet can be appropriately adjusted depending on the application, but from the viewpoint of exerting the effect of reinforcing the adherend, the total thickness of the laminate sheet is preferably 50 μm or more.
[0026] The thickness of the fiber layer of the laminate sheet is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more. The thickness of the fiber layer is preferably 500 μm or less, more preferably 200 μm or less, and even more preferably 100 μm or less. Here, the thickness of the fiber layer constituting the laminate sheet is a value measured by cutting out a cross section of the laminate sheet using an ultramicrotome UC-7 (manufactured by JEOL) and observing the cross section with an electron microscope, a magnifying glass, or visually. When the laminate sheet includes multiple fiber layers, it is preferable that the total thickness of the fiber layers is within the above range.
[0027] The thickness of the resin layer of the laminate sheet is preferably 0.5 μm or more, more preferably 1 μm or more, even more preferably 2 μm or more, and particularly preferably 3 μm or more. The thickness of the resin layer is preferably 15,000 μm or less, more preferably 5,000 μm or less, and even more preferably 500 μm or less. Here, the thickness of the resin layer constituting the laminate sheet is a value measured by cutting out a cross section of the laminate sheet using an ultramicrotome UC-7 (manufactured by JEOL) and observing the cross section with an electron microscope, a magnifying glass, or visually. When the laminate sheet contains multiple resin layers, it is preferable that the total thickness of the resin layers is within the above range.
[0028] The ratio of the thickness of the resin layer to the thickness of the fiber layer (thickness of the resin layer / thickness of the fiber layer) is preferably 10 or less, more preferably 5 or less, and even more preferably 1 or less. For example, when the resin layer is a coating layer formed by coating, the ratio of the thickness of the resin layer to the thickness of the fiber layer (thickness of the resin layer / thickness of the fiber layer) may be 0.5 or less, 0.2 or less, 0.15 or less, or 0.1 or less. In addition, when a laminate sheet has a plurality of fiber layers, the thickness of the fiber layer is the total thickness of the fiber layers, and when a plurality of resin layers is present, the thickness of the resin layer is the total thickness of the resin layers.
[0029] In this embodiment, the YI value of the laminate sheet is preferably 2.0 or less, more preferably 1.5 or less. The lower limit of the YI value of the laminate sheet is not particularly limited, but is preferably 0.1 or more. Here, the YI value of the laminate sheet is a YI value measured in accordance with JIS K 7373:2006. As a measuring device for the YI value, for example, Colour Cute i (manufactured by Suga Test Instruments Co., Ltd.) can be used. The above-mentioned YI value is a YI value measured before heating the laminate sheet as described later, and is therefore sometimes called an initial YI value.
[0030] In this embodiment, the YI value after heating the laminate sheet at 160° C. for 6 hours is preferably 20 or less, more preferably 15 or less, and even more preferably 10 or less. The lower limit of the YI value of the laminate sheet after heating at 160° C. for 6 hours is not particularly limited, but is preferably 0.1 or more. The YI value after heating at 160° C. for 6 hours is sometimes called the post-heating YI value.
[0031] The YI increase rate in the laminate sheet of this embodiment is preferably 1500% or less, more preferably 1250% or less, even more preferably 1000% or less, even more preferably 800% or less, and particularly preferably 600% or less. The lower limit of the YI increase rate in the laminate sheet is not particularly limited, but is preferably 0.1% or more. Here, the YI increase rate of the laminate sheet is the increase rate of the YI value of the laminate sheet before and after heating the laminate sheet at 160°C for 6 hours. Specifically, the YI increase rate is a value calculated by the following formula. YI increase rate (%) = (YI value of laminated sheet after heating - YI value of laminated sheet before heating) / YI value of laminated sheet before heating × 100 In the above formula, the YI value of the laminate sheet is a YI value measured in accordance with JIS K 7373:2006.
[0032] (Resin layer) The laminated sheet has at least one resin layer. Here, the resin layer is directly laminated on the fiber layer, and the resin layer and the fiber layer are in contact with each other on one side. The resin layer is preferably a resin layer formed by coating (coated resin layer).
[0033] The resin layer is a layer whose main component is a natural resin or a synthetic resin. Here, the main component refers to a component contained in an amount of 50% by mass or more with respect to the total mass of the resin layer. The resin content is preferably 60% by mass or more with respect to the total mass of the resin layer, more preferably 70% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more. The resin content may be 100% by mass or may be 95% by mass or less.
[0034] Examples of natural resins include rosin-based resins such as rosin, rosin ester, and hydrogenated rosin ester.
[0035] The synthetic resin is preferably at least one selected from, for example, polycarbonate resin, polyethylene terephthalate resin, polyethylene naphthalate resin, polyethylene resin, polypropylene resin, cyclic olefin resin, polyimide resin, polystyrene resin, and acrylic resin. Among them, the synthetic resin is preferably at least one selected from polycarbonate resin and acrylic resin, and more preferably polycarbonate resin. The acrylic resin is preferably at least one selected from polyacrylonitrile and poly(meth)acrylate.
[0036] Examples of the polycarbonate resin constituting the resin layer include aromatic polycarbonate resins and aliphatic polycarbonate resins. Specific examples of these polycarbonate resins are known, and examples of such polycarbonate resins include the polycarbonate resins described in JP 2010-023275 A.
[0037] In the laminate sheet of the present invention, the resin layer preferably contains an adhesion aid. Examples of the adhesion aid include a compound containing at least one selected from an isocyanate group, a carbodiimide group, an epoxy group, an oxazoline group, an amino group, a silanol group, and an alkoxysilyl group, and an organosilicon compound. Among them, the adhesion aid is preferably at least one selected from a compound containing an isocyanate group (isocyanate compound) and an organosilicon compound. Examples of the organosilicon compound include a silane coupling agent condensate and a silane coupling agent.
[0038] The isocyanate compound may be a polyisocyanate compound or a polyfunctional isocyanate.Specific examples of the polyisocyanate compound include aromatic polyisocyanates having 6 to 20 carbon atoms excluding the carbon in the NCO group, aliphatic polyisocyanates having 2 to 18 carbon atoms, alicyclic polyisocyanates having 6 to 15 carbon atoms, aralkyl polyisocyanates having 8 to 15 carbon atoms, modified products of these polyisocyanates, and mixtures of two or more of these.Among these, alicyclic polyisocyanates having 6 to 15 carbon atoms, i.e., isocyanurates, are preferably used.
[0039] Specific examples of alicyclic polyisocyanates include isophorone diisocyanate (IPDI), dicyclohexylmethane-4,4'-diisocyanate (hydrogenated MDI), cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, bis(2-isocyanatoethyl)-4-cyclohexene-1,2-dicarboxylate, 2,5-norbornane diisocyanate, and 2,6-norbornane diisocyanate.
[0040] The organosilicon compound may be a compound having a siloxane structure or a compound that forms a siloxane structure by condensation. For example, the organosilicon compound may be a silane coupling agent or a condensate of a silane coupling agent. The silane coupling agent may have a functional group other than an alkoxysilyl group, or may not have any other functional group. The functional group other than an alkoxysilyl group may be a vinyl group, an epoxy group, a styryl group, a methacryloxy group, an acryloxy group, an amino group, a ureido group, a mercapto group, a sulfide group, an isocyanate group, etc. The silane coupling agent used in this embodiment is preferably a silane coupling agent containing a methacryloxy group.
[0041] Specific examples of silane coupling agents having methacryloxy groups in the molecule include methacryloxypropylmethyldimethoxysilane, methacryloxypropyltrimethoxysilane, methacryloxypropylmethyldiethoxysilane, methacryloxypropyltriethoxysilane, 1,3-bis(3-methacryloxypropyl)tetramethyldisiloxane, etc. Among them, at least one selected from methacryloxypropyltrimethoxysilane, methacryloxypropyltriethoxysilane, and 1,3-bis(3-methacryloxypropyl)tetramethyldisiloxane is preferably used. The silane coupling agent preferably contains three or more alkoxysilyl groups.
[0042] Silane coupling agents may be used that have an alkoxysilyl group, or may be used that generate a silanol group after hydrolysis. In this case, it is preferable that at least a part of the alkoxysilyl group and the silanol group still exists after laminating the fiber layer. Since the silanol group is a hydrophilic group, the adhesion between the resin layer and the fiber layer can be more effectively improved by increasing the hydrophilicity of the surface of the resin layer facing the fiber layer.
[0043] The adhesion aid may be contained in a state of being uniformly dispersed in the resin layer. Here, the state where the adhesion aid is uniformly dispersed in the resin layer refers to a state where the concentration of any two regions is not more than two times higher than the concentration of the other two regions when the concentrations of the adhesion aid are measured in the following three regions ((a) to (c)): (a) The region from the surface of the resin layer facing the fiber layer to 10% of the total thickness of the resin layer (b) A region from the surface of the resin layer opposite the surface of the fiber layer to 10% of the total thickness of the resin layer. (c) An area within ±5% (total 10%) of the total thickness from the center plane of the resin layer in the thickness direction
[0044] The adhesion aid may be unevenly distributed in the region of the resin layer on the fiber layer side. For example, when an organosilicon compound is used as the adhesion aid, the organosilicon compound may be unevenly distributed in the region of the resin layer on the fiber layer side. Here, the state in which the resin layer is unevenly distributed in the region on the fiber layer side refers to a state in which, when the two concentrations in the following regions ((d) and (e)) are measured, the difference between these concentrations is two-fold or more. (d) A region from the surface of the resin layer facing the fiber layer to 10% of the total thickness of the resin layer (e) An area within ±5% (total 10%) of the total thickness from the center plane of the resin layer in the thickness direction Here, the concentration of the adhesion aid is a value measured by an X-ray electron spectrometer or an infrared spectrophotometer, and is a value obtained by cutting out a cross-section of a specified area of the laminated sheet with an ultramicrotome UC-7 (manufactured by JEOL) and measuring the cross-section with the same device.
[0045] An organosilicon compound-containing layer may be provided on the surface of the resin layer facing the fiber layer, and such a state is also included in the state in which the organosilicon compound is unevenly distributed in the region of the resin layer facing the fiber layer. The organosilicon compound-containing layer may be a coating layer formed by applying an organosilicon compound-containing coating liquid. In addition, when an organosilicon compound-containing layer is provided on the surface of the resin layer facing the fiber layer, in the above region (d), "the surface of the resin layer facing the fiber layer" shall be read as "the exposed surface of the organosilicon compound-containing layer", and "the entire thickness of the resin layer" shall be read as "the combined thickness of the resin layer and the organosilicon compound-containing layer".
[0046] The content of the adhesion assistant is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, relative to 100 parts by mass of the resin contained in the resin layer, and is preferably 40 parts by mass or less, more preferably 35 parts by mass or less, relative to 100 parts by mass of the resin contained in the resin layer. When the adhesion aid is an isocyanate compound, the content of the isocyanate compound is preferably 10 parts by mass or more, more preferably 15 parts by mass or more, and even more preferably 18 parts by mass or more, relative to 100 parts by mass of the resin contained in the resin layer. The content of the isocyanate compound is preferably 40 parts by mass or less, more preferably 35 parts by mass or less, and even more preferably 30 parts by mass or less, relative to 100 parts by mass of the resin contained in the resin layer. When the adhesion assistant is an organosilicon compound, the content of the organosilicon compound is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, based on 100 parts by mass of the resin contained in the resin layer, and is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, based on 100 parts by mass of the resin contained in the resin layer. By setting the content of the adhesion assistant within the above range, the adhesion between the fiber layer and the resin layer can be more effectively improved.
[0047] When the adhesion aid is an isocyanate compound, the content of the isocyanate group contained in the resin layer is preferably 0.5 mmol / g or more, more preferably 0.6 mmol / g or more, even more preferably 0.8 mmol / g or more, and particularly preferably 0.9 mmol / g or more. The content of the isocyanate group contained in the resin layer is preferably 3.0 mmol / g or less, more preferably 2.5 mmol / g or less, even more preferably 2.0 mmol / g or less, and particularly preferably 1.5 mmol / g or less.
[0048] The surface of the resin layer facing the fiber layer may be subjected to a surface treatment. Examples of the surface treatment method include corona treatment, plasma discharge treatment, UV irradiation treatment, electron beam irradiation treatment, and flame treatment. Among them, the surface treatment is preferably at least one selected from corona treatment and plasma discharge treatment. The plasma discharge treatment is preferably vacuum plasma discharge treatment.
[0049] The surface of the resin layer facing the fiber layer may have a fine uneven structure. The surface of the resin layer facing the fiber layer has a fine uneven structure, which can more effectively increase the adhesion between the fiber layer and the resin layer. When the surface of the resin layer facing the fiber layer has a fine uneven structure, such a structure is preferably formed by a treatment process such as blast processing, embossing processing, etching, corona treatment, plasma discharge treatment, etc. In this specification, the fine uneven structure refers to a structure in which the number of recesses present on a line of 1 mm length drawn at any position is 10 or more. When measuring the number of recesses, the laminated sheet is immersed in ion-exchanged water for 24 hours, and then the fiber layer is peeled off from the resin layer. Then, the surface of the resin layer facing the fiber layer can be measured by scanning it with a stylus surface roughness meter (manufactured by Kosaka Laboratory, Surfcorder series). When the pitch of the projections and recesses is extremely small, on the order of submicrons or nanometers, the number of projections and recesses can be measured from images observed with a scanning probe microscope (Hitachi High-Tech Science Corporation, AFM5000II and AFM5100N).
[0050] The resin layer may contain optional components other than the synthetic resin, such as fillers, pigments, dyes, and ultraviolet absorbers, which are known components used in the field of resin films.
[0051] (fiber layer) The fiber layer contains fibrous cellulose having an amount of substituents introduced of less than 0.5 mmol / g and a fiber width of 1 to 10 nm. Generally, fibrous cellulose having a fiber width of 1000 nm or less is also called fine fibrous cellulose or CNF. However, the fibrous cellulose contained in the fiber layer of the present invention is fine fibrous cellulose having an even smaller fiber width.
[0052] In this embodiment, the density of the fiber layer is 1.0 g / cm 3 It is preferable that the content is 1.2 g / cm or more. 3 More preferably, it is 1.4 g / cm or more. 3 It is more preferable that the density of the fiber layer is 1.7 g / cm or more. 3It is preferable that the density is 1.65 g / cm or less. 3 More preferably, it is 1.6 g / cm or less. 3 It is more preferable that the density is not more than 100%. When the laminate sheet contains two or more fiber layers, it is preferable that the density of each fiber layer is within the above range.
[0053] The density of the fiber layer is calculated from the basis weight and thickness of the fiber layer in accordance with JIS P 8118: 2014. The basis weight of the fiber layer can be calculated in accordance with JIS P 8124: 2011 by cutting the laminated sheet with an ultramicrotome UC-7 (manufactured by JEOL) so that only the fiber layer remains. When the fiber layer contains any component other than fine fibrous cellulose, the density of the fiber layer is the density including the optional component other than fine fibrous cellulose.
[0054] In this embodiment, the fiber layer is preferably a non-porous layer. Here, the fiber layer being non-porous means that the density of the entire fiber layer is 1.0 g / cm 3 The density of the entire fiber layer is 1.0 g / cm or more. 3 If the porosity is equal to or greater than this value, it means that the porosity of the fibrous layer is suppressed to a predetermined value or less, and the fibrous layer is distinguished from a porous sheet or layer. In addition, a fibrous layer is characterized as being non-porous by a porosity of 15 volume % or less. The porosity of the fibrous layer referred to here is calculated simply by the following formula (a): Formula (a): Porosity (volume%) = {1-B / (M×A×t)}×100 where A is the area of the fiber layer (cm 2 ), t is the thickness of the fiber layer (cm), B is the mass of the fiber layer (g), and M is the density of cellulose.
[0055] In this embodiment, the surface roughness of at least one surface of the fiber layer is preferably 50 nm or less, more preferably 30 nm or less, and even more preferably 10 nm or less. It is particularly preferable that the surface roughness of both surfaces of the fiber layer is within the above range. By setting the surface roughness within the above range, the transparency of the fiber layer can be further increased, and as a result, the transparency of the laminated sheet can also be increased. Specifically, the haze of the fiber layer and the laminated sheet can be further reduced. Here, the surface roughness (arithmetic mean) of the fiber layer is the arithmetic mean roughness of at least one surface of the fiber layer. The surface roughness (arithmetic mean) is a value obtained by measuring the arithmetic mean roughness of a 3 μm square area using an atomic force microscope (NanoScope IIIa, manufactured by Veeco).
[0056] In this embodiment, the surface pH of the fiber layer is preferably 3 or more, more preferably 4 or more, and even more preferably 5 or more. The surface pH of the fiber layer is preferably 10 or less, more preferably 9 or less, and even more preferably 8 or less. By setting the surface pH of the fiber layer within the above range, it is easy to obtain the effect of suppressing yellowing. In order to set the surface pH of the fiber layer within the above range, it is preferable to appropriately adjust the pH of the fine fibrous cellulose dispersion obtained in the manufacturing process described below. When measuring the surface pH of the fiber layer, 10 μL of ion-exchanged water is dropped into a 1 cm square area on the surface of the fiber layer with a micropipette, and the pH of that area is measured using a flat pH composite electrode (6261-10C; manufactured by HORIBA).
[0057] <Fine fibrous cellulose> In this embodiment, the amount of substituents introduced into the fine fibrous cellulose may be less than 0.5 mmol / g, preferably 0.4 mmol / g or less, more preferably 0.3 mmol / g or less, even more preferably 0.25 mmol / g or less, and particularly preferably 0.15 mmol / g or less. The amount of substituents introduced into the fine fibrous cellulose may be 0.0 mmol / g, but is preferably 0.03 mmol / g or more, more preferably 0.04 mmol / g or more, even more preferably 0.05 mmol / g or more, and particularly preferably 0.07 mmol / g or more.
[0058] The fiber width of the fine fibrous cellulose may be 1 to 10 nm, preferably 1 to 9 nm, more preferably 1 to 8 nm, and even more preferably 1 to 7 nm. Here, the fiber width of the fine fibrous cellulose is measured, for example, by observation with an electron microscope as follows. First, the fine fibrous cellulose is dispersed in water so that the cellulose concentration is 0.01% by mass or more and 0.1% by mass or less, and cast on a carbon film-coated grid that has been hydrophilized. After drying, the grid is stained with uranyl acetate and observed with a transmission electron microscope (TEM, manufactured by JEOL-2000EX, manufactured by JEOL Co., Ltd.). In this case, an axis of any image width in the vertical and horizontal directions is assumed in the obtained image, and the magnification is adjusted so that 20 or more fibers cross the axis. After obtaining an observation image that satisfies this condition, two random axes are drawn vertically and horizontally on the image, and the fiber width of the fibers crossing the axis is visually read. In this way, three non-overlapping observation images are taken, and the fiber width values of the fibers intersecting the two axes are read for each image (20 or more fibers x 2 x 3 = 120 or more fibers). (1) A straight line X is drawn at any point within the observed image, and 20 or more fibers intersect with the straight line X. (2) Within the same image, draw a line Y that intersects the line perpendicularly, and have 20 or more fibers intersect with the line Y.
[0059] For the fine fibrous cellulose contained in the fiber layer, the number average fiber width can be calculated from the fiber width obtained by the above method. The number average fiber width of the fibrous cellulose contained in the fiber layer is preferably 1 to 10 nm, more preferably 1 to 9 nm, even more preferably 1 to 8 nm, and particularly preferably 1 to 7 nm. The number average fiber width of the fibrous cellulose contained in the fiber layer being within the above range means that the fiber layer does not substantially contain coarse cellulose fibers, and furthermore, 70% or more of the fibrous cellulose has a fiber width of 10 nm or less. The proportion of the fine fibrous cellulose having a fiber width of 10 nm or less among the total fibrous cellulose contained in the fiber layer is preferably 70% or more, more preferably 80% or more, and even more preferably 90% or more. Here, the proportion of fine fibrous cellulose having a fiber width of 10 nm or less is a value represented by the following formula. Percentage of fine fibrous cellulose with a fiber width of 10 nm or less (%) = (number of fine fibrous cellulose with a fiber width of 10 nm or less / total number of fibrous cellulose) x 100
[0060] The fiber width of the fine fibrous cellulose in the laminate sheet is measured, for example, using atomic force microscope observation as follows. First, the fiber layer of the laminate sheet is observed using an atomic force microscope (NanoScope IIIa, manufactured by Veeco). The image is taken at a viewing angle of 500 nm. For the obtained image, two random axes are drawn vertically and horizontally per image, and 20 or more fibers that cross the axes are randomly selected and the fiber width is read visually. In this way, three non-overlapping observation images are taken, and the fiber width values of the fibers that cross each of the two axes are read. (20 or more x 2 x 3 = 120 or more) (1) Draw a straight line X at any point within the observed image, and randomly select 20 or more fibers that intersect with the straight line X. (2) Within the same image, draw a line Y that intersects the line perpendicularly, and randomly select 20 or more fibers that intersect with line Y. When the fiber layer is not exposed in the laminated sheet, the laminated sheet is cut using an ultramicrotome or the like to cut out a cross section of the fiber layer, and the cross section is observed by the above-mentioned method.
[0061] The fiber length of the fine fibrous cellulose is not particularly limited, but is preferably 0.1 μm or more and 1000 μm or less, more preferably 0.1 μm or more and 800 μm or less, and even more preferably 0.1 μm or more and 600 μm or less. By setting the fiber length within the above range, destruction of the crystalline region of the fine fibrous cellulose can be suppressed. In addition, it is also possible to set the slurry viscosity of the fine fibrous cellulose to an appropriate range. The fiber length of the fine fibrous cellulose can be determined, for example, by image analysis using TEM, SEM, or AFM.
[0062] The fine fibrous cellulose preferably has an I-type crystal structure. The fact that the fine fibrous cellulose has an I-type crystal structure can be identified from a diffraction profile obtained from a wide-angle X-ray diffraction photograph using CuKα (λ=1.5418 Å) monochromatized with graphite. Specifically, it can be identified from the presence of typical peaks at two positions, around 2θ=14° to 17° and around 2θ=22° to 23°. The proportion of I-type crystal structure in the fine fibrous cellulose is, for example, preferably 30% or more, more preferably 40% or more, and even more preferably 50% or more. The degree of crystallinity can be determined by measuring an X-ray diffraction profile and using the pattern in a conventional manner (Seagal et al., Textile Research Journal, Vol. 29, p. 786, 1959).
[0063] The axial ratio (fiber length / fiber width) of the fine fibrous cellulose is not particularly limited, but is preferably, for example, from 50 to 10,000, and more preferably from 100 to 1,000. By setting the axial ratio to the above lower limit or more, a sheet containing the fine fibrous cellulose can be easily formed. By setting the axial ratio to the above upper limit or less, it is preferable in that, for example, when the fibrous cellulose is treated as a dispersion liquid, handling such as dilution is facilitated.
[0064] The fine fibrous cellulose in this embodiment has, for example, both crystalline and non-crystalline regions. Fine fibrous cellulose having both crystalline and non-crystalline regions and having an axial ratio within the above range is realized by the method for producing fine fibrous cellulose described later.
[0065] The cellulose components in the fine fibrous cellulose can be classified into α-cellulose components and hemicellulose components. A lower ratio of hemicellulose is preferable because it is easier to obtain the effect of suppressing yellowing over time and yellowing due to heat. The ratio of hemicellulose in the fine fibrous cellulose of the present invention is preferably less than 30%, more preferably less than 25%, and even more preferably less than 20%.
[0066] The total amount of nitrogen contained in the fine fibrous cellulose and the free nitrogen contained in the fine fibrous cellulose dispersion (hereinafter sometimes referred to as "nitrogen amount", "nitrogen amount contained in fine fibrous cellulose", or "nitrogen amount in fine fibrous cellulose") is preferably 0.08 mmol / g or less, more preferably 0.04 mmol / g or less, and even more preferably 0.02 mmol / g or less. The amount of nitrogen contained in the fine fibrous cellulose is preferably 0.001 mmol / g or more. The amount of nitrogen in the fine fibrous cellulose is a value measured by the following method. First, a dispersion containing fine fibrous cellulose is adjusted to a solid content concentration of 1 mass% and decomposed by the Kjeldahl method (JIS K 0102 2016 44.1). After decomposition, the amount of ammonium ions (mmol) is measured by cation chromatography, and the nitrogen content (mmol / g) is calculated by dividing by the amount of cellulose (g) used in the measurement. The above-mentioned amount of nitrogen is the total amount of nitrogen bound to the fine fibrous cellulose by ionic bonds and / or covalent bonds and free nitrogen dissolved in the dispersion that is not bound to the fine fibrous cellulose by ionic bonds and / or covalent bonds.
[0067] In this embodiment, the amount of substituents introduced into the fine fibrous cellulose is less than 0.5 mmol / g, and the substituents referred to here are preferably anionic groups. That is, the fine fibrous cellulose of the present invention is obtained by subjecting fine fibrous cellulose having an anionic group to a substituent removal treatment, and the fine fibrous cellulose of the present invention is substituent-removed fine fibrous cellulose.
[0068] Examples of the anionic group include phosphorus oxoacid groups or substituents derived from phosphorus oxoacid groups (sometimes simply referred to as phosphorus oxoacid groups), carboxy groups or substituents derived from carboxy groups (sometimes simply referred to as carboxy groups), sulfone groups or substituents derived from sulfone groups (sometimes simply referred to as sulfone groups), and xanthate groups or substituents derived from xanthate groups (sometimes simply referred to as xanthate groups). When a sulfone group or a substituent derived from a sulfone group is introduced via an ester bond, the substituent may be referred to as a sulfur oxoacid group or a substituent derived from a sulfur oxoacid group (sometimes simply referred to as a sulfur oxoacid group). Among these, the anionic group is preferably at least one selected from phosphorus oxoacid groups or substituents derived from phosphorus oxoacid groups, and sulfone groups or substituents derived from sulfone groups, and more preferably a phosphorus oxoacid group or a substituent derived from a phosphorus oxoacid group.
[0069] The phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group is, for example, a substituent represented by the following formula (1). A plurality of substituents represented by the following formula (1) may be introduced into each fine fibrous cellulose. In this case, the plurality of introduced substituents represented by the following formula (1) may be the same or different.
[0070] [ka]
[0071] In formula (1), a, b, and n are natural numbers, and m is an arbitrary number (where a=b×m). At least one of the n α and α' is O. - and the rest are R or OR. Note that all of α and α' are O - The n α's may all be the same or may be different. b+ is a cation of one or more valences consisting of organic or inorganic substances.
[0072] R is a hydrogen atom, a saturated linear hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated linear hydrocarbon group, an unsaturated branched hydrocarbon group, an unsaturated cyclic hydrocarbon group, an aromatic group, or a group derived therefrom. In formula (1), n is preferably 1.
[0073] Examples of saturated linear hydrocarbon groups include, but are not limited to, methyl, ethyl, n-propyl, or n-butyl groups. Examples of saturated branched hydrocarbon groups include, but are not limited to, i-propyl or t-butyl groups. Examples of saturated cyclic hydrocarbon groups include, but are not limited to, cyclopentyl or cyclohexyl groups. Examples of unsaturated linear hydrocarbon groups include, but are not limited to, vinyl or allyl groups. Examples of unsaturated branched hydrocarbon groups include, but are not limited to, i-propenyl or 3-butenyl groups. Examples of unsaturated cyclic hydrocarbon groups include, but are not limited to, cyclopentenyl or cyclohexenyl groups. Examples of aromatic groups include, but are not limited to, phenyl or naphthyl groups.
[0074] In addition, the derivative group in R is a carboxy group, a carboxylate group (-COO - ), a functional group in which at least one selected from functional groups such as a hydroxyl group, an amino group, and an ammonium group is added or substituted, but is not particularly limited. The number of carbon atoms constituting the main chain of R is not particularly limited, but is preferably 20 or less, and more preferably 10 or less. By setting the number of carbon atoms constituting the main chain of R within the above range, the molecular weight of the phosphorus oxoacid group can be set to an appropriate range, which facilitates penetration into the fiber raw material and increases the yield of fine cellulose fiber. When multiple Rs are present in formula (1) or multiple types of substituents represented by the above formula (1) are introduced into the fine fibrous cellulose, the multiple Rs may be the same or different.
[0075] βb+ is a monovalent or higher cation made of an organic or inorganic substance. An example of the monovalent or higher cation made of an organic substance is an organic onium ion. An example of the organic onium ion is an organic ammonium ion or an organic onium ion. An example of the organic ammonium ion is an aliphatic ammonium ion or an aromatic ammonium ion, and an example of the organic onium ion is an aliphatic phosphonium ion or an aromatic phosphonium ion. An example of the monovalent or higher cation made of an inorganic substance is an ion of an alkali metal such as sodium, potassium, or lithium, an ion of a divalent metal such as calcium or magnesium, a hydrogen ion, an ammonium ion, or the like. In addition, in formula (1), β b+ When a plurality of β b+ may be the same or different. The organic or inorganic cations of monovalent or higher are β b+ Sodium or potassium ions are preferred because they are less likely to yellow when the fiber raw material containing the cation is heated and are easy to use industrially, but there is no particular limitation.
[0076] More specifically, examples of the phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group include a phosphoric acid group (-PO3H2), a salt of a phosphoric acid group, a phosphorous acid group (phosphonic acid group) (-PO2H2), and a salt of a phosphorous acid group (phosphonic acid group). In addition, the phosphorus oxoacid group or the substituent derived from the phosphorus oxoacid group may be a group in which a phosphoric acid group is condensed (e.g., a pyrophosphate group), a group in which a phosphonic acid is condensed (e.g., a polyphosphonic acid group), a phosphoric ester group (e.g., a monomethyl phosphate group, a polyoxyethylene alkyl phosphate group), an alkyl phosphonic acid group (e.g., a methyl phosphonic acid group), and the like.
[0077] Moreover, the sulfone group (sulfone group or a substituent derived from a sulfone group) is preferably a sulfur oxoacid group (sulfur oxoacid group or a substituent derived from a sulfur oxoacid group), and is preferably, for example, a substituent represented by the following formula (2). A plurality of substituents represented by the following formula (2) may be introduced into each fine fibrous cellulose. In this case, the plurality of introduced substituents represented by the following formula (2) may be the same or different.
[0078] [ka]
[0079] In the above structural formula, b and n are natural numbers, p is 0 or 1, and m is an arbitrary number (where 1=b×m). When n is 2 or more, the multiple p's may be the same or different. In the above structural formula, β b+ is a monovalent or higher cation made of an organic or inorganic substance. An example of the monovalent or higher cation made of an organic substance is an organic onium ion. An example of the organic onium ion is an organic ammonium ion or an organic onium ion. An example of the organic ammonium ion is an aliphatic ammonium ion or an aromatic ammonium ion, and an example of the organic onium ion is an aliphatic phosphonium ion or an aromatic phosphonium ion. An example of the monovalent or higher cation made of an inorganic substance is an ion of an alkali metal such as sodium, potassium, or lithium, an ion of a divalent metal such as calcium or magnesium, a hydrogen ion, an ammonium ion, or the like. When multiple types of substituents represented by the above formula (2) are introduced into the fine fibrous cellulose, the multiple β b+ may be the same or different. The organic or inorganic cations of monovalent or higher are β b+ The ion is preferably sodium or potassium ion, which is less likely to yellow when the fiber raw material containing the cation is heated and is easy to use industrially, but is not particularly limited.
[0080] The amount of anionic groups introduced into the fine fibrous cellulose can be measured, for example, by neutralization titration, in which an alkali such as an aqueous sodium hydroxide solution is added to a slurry containing the obtained fine fibrous cellulose to determine the change in pH, thereby measuring the amount introduced.
[0081] 2 is a graph showing the relationship between the amount of NaOH dropped onto a slurry containing fine fibrous cellulose having phosphorus oxo acid groups and pH. The amount of phosphorus oxo acid groups introduced into the fine fibrous cellulose is measured, for example, as follows. First, a slurry containing fine fibrous cellulose is treated with a strongly acidic ion exchange resin. If necessary, the measurement target may be subjected to a defibration treatment similar to the defibration treatment step described below prior to the treatment with the strongly acidic ion exchange resin. Next, the change in pH is observed while adding the aqueous sodium hydroxide solution, and a titration curve such as that shown in the upper part of Figure 2 is obtained. In the titration curve shown in the upper part of Figure 2, the measured pH is plotted against the amount of alkali added, and in the titration curve shown in the lower part of Figure 2, the increment (derivative value) of pH (1 / mmol) against the amount of alkali added is plotted. In this neutralization titration, two points are confirmed in the curve plotting the measured pH against the amount of alkali added, where the increment (derivative value of pH with respect to the amount of alkali added) is maximum. Of these, the first maximum point of the increment obtained after starting to add the alkali is called the first endpoint, and the next maximum point of the increment is called the second endpoint. The amount of alkali required from the start of titration to the first end point is equal to the amount of the first dissociated acid of the fine fibrous cellulose contained in the slurry used for titration, the amount of alkali required from the first end point to the second end point is equal to the amount of the second dissociated acid of the fine fibrous cellulose contained in the slurry used for titration, and the amount of alkali required from the start of titration to the second end point is equal to the total dissociated acid of the fine fibrous cellulose contained in the slurry used for titration. The value obtained by dividing the amount of alkali required from the start of titration to the first end point by the solid content (g) in the slurry to be titrated is the amount of phosphorus oxoacid group introduced (mmol / g). Note that when simply referring to the amount of phosphorus oxoacid group introduced (or the amount of phosphorus oxoacid group), it refers to the amount of the first dissociated acid. In FIG. 2, the region from the start of titration to the first end point is called the first region, and the region from the first end point to the second end point is called the second region. For example, when the phosphorus oxoacid group is a phosphate group and this phosphate group undergoes condensation, the amount of weak acid groups in the phosphorus oxoacid group (also referred to as the second dissociated acid amount in this specification) appears to decrease, and the amount of alkali required in the second region becomes smaller than the amount of alkali required in the first region. On the other hand, the amount of strong acid groups in the phosphorus oxoacid group (also referred to as the first dissociated acid amount in this specification) is equal to the amount of phosphorus atoms regardless of the presence or absence of condensation. In addition, when the phosphorus oxoacid group is a phosphorous acid group, the phosphorus oxoacid group no longer has weak acid groups, so the amount of alkali required in the second region becomes smaller or may become zero. In this case, there is only one point on the titration curve where the pH increment is maximum.
[0082] The above-mentioned amount of phosphorus oxoacid groups introduced (mmol / g) indicates the amount of phosphorus oxoacid groups possessed by the acid-type fine fibrous cellulose (hereinafter referred to as the amount of phosphorus oxoacid groups (acid type)), since the denominator indicates the mass of the acid-type fine fibrous cellulose. On the other hand, when the counter ion of the phosphorus oxoacid group is replaced with any cation C so as to be the charge equivalent, the amount of phosphorus oxoacid groups possessed by the fine fibrous cellulose in which the cation C is the counter ion (hereinafter referred to as the amount of phosphorus oxoacid groups (C type)) can be obtained by converting the denominator to the mass of the fine fibrous cellulose when the cation C is the counter ion. That is, it is calculated according to the following formula. Amount of phosphorus oxoacid group (C type) = Amount of phosphorus oxoacid group (acid type) / {1+(W-1)×A / 1000} A [mmol / g]: Total amount of anions derived from phosphorus oxoacid groups in fine fibrous cellulose (total amount of dissociated acid from phosphorus oxoacid groups) W: Formula weight per valence of cation C (for example, Na is 23, Al is 9)
[0083] In the measurement of the amount of anionic groups by titration, if the amount of sodium hydroxide solution dropped is too large or the titration interval is too short, the amount of anionic groups may be lower than the actual amount, and an accurate value may not be obtained. As an appropriate amount of drop and titration interval, for example, it is preferable to titrate 10 to 50 μL of 0.1N sodium hydroxide solution every 5 to 30 seconds. In addition, in order to eliminate the influence of carbon dioxide dissolved in the slurry containing fine fibrous cellulose, it is preferable to measure while blowing an inert gas such as nitrogen gas into the slurry from 15 minutes before the start of titration until the end of titration.
[0084] The amount of sulfonic groups introduced into the fine fibrous cellulose can be calculated by freeze-drying a slurry containing the fine fibrous cellulose, pulverizing the slurry, and measuring the amount of sulfur in the resulting pulverized sample. Specifically, the slurry containing the fine fibrous cellulose is freeze-dried, and the resulting pulverized sample is subjected to pressurized heat decomposition using nitric acid in a closed container, and then appropriately diluted and the amount of sulfur is measured by ICP-OES. The value calculated by dividing the amount by the bone dry mass of the fine fibrous cellulose used is taken as the amount of sulfonic groups in the fine fibrous cellulose (unit: mmol / g).
[0085] The amount of xanthate group introduced into the fine fibrous cellulose can be measured by the Bredee method using the following method. First, 40 mL of saturated ammonium chloride solution is added to 1.5 parts by mass (absolute dry mass) of fine fibrous cellulose, the sample is crushed with a glass rod and mixed well, and then left for about 15 minutes, filtered with GFP filter paper (GS-25 manufactured by ADVANTEC), and thoroughly washed with saturated ammonium chloride solution. Next, the sample is placed in a 500 mL tall beaker together with the GFP filter paper, 50 mL of 0.5 M sodium hydroxide solution (5 ° C.) is added, stirred, and left for 15 minutes. Phenolphthalein solution is added until the solution turns pink, and then 1.5 M acetic acid is added, and the point at which the solution changes from pink to colorless is taken as the neutralization point. After neutralization, 250 mL of distilled water is added and stirred well, and 10 mL of 1.5 M acetic acid and 10 mL of 0.05 mol / L iodine solution are added using a whole pipette. Then, this solution is titrated with 0.05 mol / L sodium thiosulfate solution, and the amount of xanthate groups is calculated from the titration amount of sodium thiosulfate and the bone dry mass of the fine fibrous cellulose according to the following formula. Amount of xanthate group (mmol / g) = (0.05 x 10 x 2 - 0.05 x sodium thiosulfate titration (mL)) / 1000 / bone dry mass of fine fibrous cellulose (g)
[0086] In the present embodiment, the fine fibrous cellulose preferably has a carbamide group. In the present specification, the carbamide group is preferably a group represented by the following structural formula:
[0087] [ka]
[0088] In the above structural formula, R is a hydrogen atom, a saturated linear hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated linear hydrocarbon group, an unsaturated branched hydrocarbon group, an aromatic group, or a group derived therefrom. Among these, it is particularly preferable that R is a hydrogen atom.
[0089] The amount of carbamide groups introduced into the fine fibrous cellulose is preferably 0.001 mmol / g or more. The amount of carbamide groups introduced into the fine fibrous cellulose is preferably 0.08 mmol / g or less, more preferably 0.04 mmol / g or less, and even more preferably 0.02 mmol / g or less. Here, the amount of carbamide groups introduced into the fine fibrous cellulose can be calculated by freeze-drying a slurry containing the fine fibrous cellulose and then pulverizing the resulting sample, and subjecting the sample to a trace nitrogen analysis. The amount of carbamide groups introduced (mmol / g) per unit mass of the fine fibrous cellulose can be calculated by dividing the nitrogen content (g / g) per unit mass of the fine fibrous cellulose obtained by the trace nitrogen analysis by the atomic weight of nitrogen.
[0090] In this embodiment, when the fine fibrous cellulose used to form the fibrous layer is dispersed in water at a concentration of 0.1% by mass and the nanofiber yield is calculated by the following formula, the nanofiber yield is preferably 95% by mass or more, and more preferably 96% by mass or more. The nanofiber yield may be 100% by mass. Nanofiber yield [mass%] = C / 0.1 × 100 Here, C is the concentration of fine fibrous cellulose contained in the supernatant obtained when an aqueous dispersion containing 0.1% by mass of fine fibrous cellulose is centrifuged at 12,000 G for 10 minutes.
[0091] In addition, in the present embodiment, when the microfibrillar cellulose used for forming the fiber layer is a water dispersion with a concentration of 0.2% by mass, the haze of the water dispersion is preferably 5.0% or less, more preferably 4.0% or less, and still more preferably 3.0% or less. Note that the haze of the water dispersion may be 0%. If the haze of the water dispersion with a concentration of 0.2% by mass is within the above range, it can be determined that the dispersion is transparent. Here, the haze of the water dispersion is a value measured in accordance with JIS K 7136:2000 using a haze meter and a glass cell for liquids with an optical path length of 1 cm. The zero-point measurement is performed using ion-exchanged water placed in the same glass cell. In addition, the dispersion to be measured is allowed to stand for 24 hours in an environment of 23°C and a relative humidity of 50% before measurement, and the liquid temperature of the dispersion is set to 23°C.
[0092] In the present embodiment, when the microfibrillar cellulose used for forming the fiber layer is a dispersion (water dispersion) with a concentration of 1% by mass, the pH of the dispersion is preferably 3 or more, more preferably 4 or more, and still more preferably 5 or more. Also, the pH of the dispersion is preferably 10 or less, more preferably 9 or less, and still more preferably 8 or less. By setting the pH of the dispersion within the above range, yellowing of the dispersion and the sheet can be more effectively suppressed. Note that in order to set the pH of the dispersion within the above range, the same method as the <pH adjustment step> described later can also be employed.
[0093] In this embodiment, when the fine fibrous cellulose used to form the fiber layer is a dispersion (aqueous dispersion) with a concentration of 0.4% by mass, the viscosity of the dispersion at 23°C is preferably 100 mPa·s or more, more preferably 1000 mPa·s or more, and even more preferably 2000 mPa·s or more. The viscosity of the dispersion at 23°C is preferably 200000 mPa·s or less, and more preferably 100000 mPa·s or less. The viscosity of a dispersion with a fine fibrous cellulose concentration of 0.4% by mass can be measured using a B-type viscometer (manufactured by BLOOKFIELD, analog viscometer T-LVT). The measurement conditions are 23°C, a rotation speed of 3 rpm, and the viscosity is measured 3 minutes after the start of the measurement. In addition, the dispersion to be measured is left to stand for 24 hours in an environment of 23°C and relative humidity 50% before the measurement, and the liquid temperature of the dispersion is set to 23°C.
[0094] The amount of free nitrogen in the dispersion containing fine fibrous cellulose used to form the fiber layer is preferably small. The amount of free nitrogen in the dispersion can be measured by measuring the nitrogen concentration in the filtrate when the fine fibrous cellulose dispersion is filtered. For example, the free nitrogen concentration in a dispersion containing 0.2% by mass of fine fibrous cellulose is preferably 100 ppm or less, more preferably 80 ppm or less, even more preferably 70 ppm or less, even more preferably 60 ppm or less, even more preferably 50 ppm or less, even more preferably 40 ppm or less, and particularly preferably 30 ppm or less. The nitrogen concentration in a dispersion containing 0.2% by mass of fine fibrous cellulose may be 0 ppm. Since free nitrogen present in the dispersion causes coloration, yellowing of the dispersion containing fine fibrous cellulose and the sheet can be more effectively suppressed by setting the nitrogen concentration in the filtrate within the above range. Here, the method for measuring the nitrogen concentration in the filtrate is as follows. First, distilled water is added so that the concentration of fine fibrous cellulose becomes 0.2% by mass, and after stirring for 24 hours, the mixture is filtered using a filter medium with a pore size of 0.45 μm to obtain a filtrate. The nitrogen concentration (ppm) in the filtrate is then measured by trace nitrogen analysis.
[0095] <Optional ingredients> The fiber layer may contain optional components other than fine fibrous cellulose. Examples of optional components include spacer molecules, hydrophilic polymers, and organic ions, as described below. The hydrophilic polymer is preferably a hydrophilic oxygen-containing organic compound (excluding the above-mentioned cellulose fibers). The oxygen-containing organic compound is preferably non-fibrous, and such non-fibrous oxygen-containing organic compounds do not include fine fibrous cellulose and thermoplastic resin fibers.
[0096] The oxygen-containing organic compound is preferably a hydrophilic organic compound. The hydrophilic oxygen-containing organic compound can improve the strength, density, chemical resistance, etc. of the fiber layer. The hydrophilic oxygen-containing organic compound preferably has an SP value of 9.0 or more. In addition, the hydrophilic oxygen-containing organic compound is preferably one in which 1 g or more of the oxygen-containing organic compound dissolves in 100 ml of ion-exchanged water.
[0097] Examples of oxygen-containing organic compounds include hydrophilic polymers such as polyethylene glycol, polyethylene oxide, casein, dextrin, starch, modified starch, polyvinyl alcohol, modified polyvinyl alcohol (acetoacetylated polyvinyl alcohol, etc.), polyethylene oxide, polyvinylpyrrolidone, polyvinyl methyl ether, polyacrylates, polyacrylamide, acrylic acid alkyl ester copolymers, urethane copolymers, and cellulose derivatives (hydroxyethyl cellulose, carboxyethyl cellulose, carboxymethyl cellulose, etc.); and hydrophilic low molecules such as glycerin, sorbitol, and ethylene glycol. Among these, from the viewpoint of improving the strength, density, chemical resistance, etc. of the fiber layer, polyethylene glycol, polyethylene oxide, polyvinyl alcohol, glycerin, and sorbitol are preferred, at least one selected from polyethylene glycol and polyethylene oxide is more preferred, and at least one selected from polyethylene oxide, polyvinyl alcohol, and polyethylene glycol is even more preferred.
[0098] The oxygen-containing organic compound is preferably an organic polymer having a molecular weight of 50,000 to 8 million. The molecular weight of the oxygen-containing organic compound is also preferably 100,000 to 5 million, but may be a low molecular weight compound having a molecular weight of less than 1,000.
[0099] The content of the oxygen-containing organic compound contained in the fiber layer is preferably 1 part by mass or more, more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more, relative to 100 parts by mass of the fine fibrous cellulose contained in the fiber layer. The content of the oxygen-containing organic compound contained in the fiber layer is preferably 1000 parts by mass or less, more preferably 500 parts by mass or less, even more preferably 100 parts by mass or less, and particularly preferably 50 parts by mass or less, relative to 100 parts by mass of the fine fibrous cellulose contained in the fiber layer. By setting the content of the oxygen-containing organic compound within the above range, a laminate sheet having high transparency and strength can be formed.
[0100] Examples of organic ions include tetraalkylammonium ions and tetraalkylphosphonium ions. Examples of tetraalkylammonium ions include tetramethylammonium ions, tetraethylammonium ions, tetrapropylammonium ions, tetrabutylammonium ions, tetrapentylammonium ions, tetrahexylammonium ions, tetraheptylammonium ions, tributylmethylammonium ions, lauryltrimethylammonium ions, cetyltrimethylammonium ions, stearyltrimethylammonium ions, octyldimethylethylammonium ions, lauryldimethylethylammonium ions, didecyldimethylammonium ions, lauryldimethylbenzylammonium ions, and tributylbenzylammonium ions. Examples of tetraalkylphosphonium ions include tetramethylphosphonium ions, tetraethylphosphonium ions, tetrapropylphosphonium ions, tetrabutylphosphonium ions, and lauryltrimethylphosphonium ions. Examples of tetrapropylonium ions and tetrabutylonium ions include tetra-n-propylonium ions and tetra-n-butylonium ions, respectively.
[0101] Further optional components include antifoaming agents, lubricants, ultraviolet absorbers, dyes, pigments, stabilizers, surfactants, preservatives (eg, phenoxyethanol), and the like.
[0102] (Method of producing fine fibrous cellulose) The above-mentioned method for producing fine fibrous cellulose includes a step (A) of removing at least a part of the substituents from fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less, and a step (B) of uniformly dispersing the cellulose after the step (A). The substituents of the fine fibrous cellulose subjected to the step (A) are preferably anionic groups, more preferably phosphorus oxo acid groups or substituents derived from phosphorus oxo acid groups. Furthermore, the fine fibrous cellulose subjected to the step (A) preferably has carbamide groups.
[0103] (Process (A)) Step (A) is a step of removing at least a part of the substituents from fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less. First, a method for producing fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less (fine fibrous cellulose to be subjected to step (A)) will be described below.
[0104] <Textile raw materials> The fine fibrous cellulose to be subjected to step (A) is produced from a fiber raw material containing cellulose. The fiber raw material containing cellulose is not particularly limited, but it is preferable to use pulp because it is easily available and inexpensive. Examples of pulp include wood pulp, non-wood pulp, and deinked pulp. Examples of wood pulp include, but are not particularly limited to, chemical pulp such as hardwood kraft pulp (LBKP), softwood kraft pulp (NBKP), sulfite pulp (SP), dissolving pulp (DP), soda pulp (AP), unbleached kraft pulp (UKP), and oxygen bleached kraft pulp (OKP), semi-chemical pulp such as semi-chemical pulp (SCP) and chemi-ground wood pulp (CGP), and mechanical pulp such as groundwood pulp (GP) and thermomechanical pulp (TMP, BCTMP), etc. The non-wood pulp is not particularly limited, but may be, for example, cotton-based pulp such as cotton linters and cotton lint, and non-wood pulp such as hemp, straw, and bagasse. The deinked pulp is not particularly limited, but may be, for example, deinked pulp made from waste paper. The pulp of this embodiment may be used alone or in combination of two or more of the above. Among the above pulps, for example, wood pulp and deinked pulp are preferred from the viewpoint of ease of availability. Furthermore, among the wood pulps, for example, chemical pulp is more preferred, and kraft pulp and sulfite pulp are even more preferred, from the viewpoint of a high cellulose ratio and a high yield of fine fibrous cellulose during defibration treatment, and the decomposition of cellulose in the pulp is small, and long-fiber fine fibrous cellulose with a large axial ratio is obtained. Note that the viscosity tends to increase when long-fiber fine fibrous cellulose with a large axial ratio is used.
[0105] As a fiber raw material containing cellulose, for example, cellulose contained in sea squirts and bacterial cellulose produced by acetic acid bacteria can be used. Also, instead of a fiber raw material containing cellulose, a fiber formed by a linear nitrogen-containing polysaccharide polymer such as chitin or chitosan can be used.
[0106] <Phosphorus oxo acid group introduction step> The fine fibrous cellulose subjected to step (A) has a substituent. For this reason, the production process of the fine fibrous cellulose subjected to step (A) preferably has a substituent introduction step, and more preferably has an anionic group introduction step. An example of the anionic group introduction step is a phosphorus oxo acid group introduction step. The phosphorus oxo acid group introduction step is a step of reacting at least one compound (hereinafter also referred to as "compound A") selected from compounds capable of introducing a phosphorus oxo acid group by reacting with a hydroxyl group possessed by a fiber raw material containing cellulose, with the fiber raw material containing cellulose. This step results in the production of a fiber into which a phosphorus oxo acid group has been introduced.
[0107] In the phosphorus oxoacid group introduction step according to this embodiment, the reaction of the cellulose-containing fiber raw material with compound A is preferably carried out in the presence of at least one selected from urea and its derivatives (hereinafter also referred to as "compound B").
[0108] An example of a method for acting compound A on a fiber raw material in the presence of compound B includes a method of mixing compound A and compound B with a fiber raw material in a dry state, a wet state, or a slurry state. Of these, it is preferable to use a fiber raw material in a dry state or a wet state, and it is particularly preferable to use a fiber raw material in a dry state, because the reaction is highly uniform. The form of the fiber raw material is not particularly limited, but it is preferable to use a cotton-like or thin sheet-like form. Compound A and compound B are each added to the fiber raw material in a powder form, a solution form dissolved in a solvent, or a melted state by heating to a melting point or higher. Of these, it is preferable to add them in a solution form dissolved in a solvent, especially in an aqueous solution form, because the reaction is highly uniform. In addition, compound A and compound B may be added to the fiber raw material simultaneously, separately, or as a mixture. The method of adding compound A and compound B is not particularly limited, but when compound A and compound B are in a solution form, the fiber raw material may be immersed in the solution to absorb the liquid and then removed, or the solution may be dropped onto the fiber raw material. In addition, the required amounts of compound A and compound B may be added to the fiber raw material, or excess amounts of compound A and compound B may be added to the fiber raw material, respectively, and then the excess compound A and compound B may be removed by squeezing or filtration.
[0109] The compound A used in this embodiment may be any compound that has a phosphorus atom and can form an ester bond with cellulose, and may include, but is not limited to, phosphoric acid or a salt thereof, phosphorous acid or a salt thereof, dehydrated condensed phosphoric acid or a salt thereof, and anhydrous phosphoric acid (diphosphorus pentoxide). Phosphoric acid may be used with various purities, for example, 100% phosphoric acid (orthophosphoric acid) or 85% phosphoric acid. Phosphorous acid may be 99% phosphorous acid (phosphonic acid). Dehydrated condensed phosphoric acid is a phosphoric acid in which two or more molecules are condensed by a dehydration reaction, and examples of such include pyrophosphoric acid and polyphosphoric acid. Phosphates, phosphites, and dehydrated condensed phosphates include lithium salts, sodium salts, potassium salts, and ammonium salts of phosphoric acid, phosphorous acid, or dehydrated condensed phosphoric acid, and these may be neutralized to various degrees. Among these, from the viewpoints of high introduction efficiency of phosphate groups, easier improvement of defibration efficiency in the defibration step described below, low cost, and ease of industrial application, phosphoric acid, sodium salt of phosphoric acid, potassium salt of phosphoric acid, ammonium salt of phosphoric acid, or phosphorous acid, sodium salt of phosphorous acid, potassium salt of phosphorous acid, or ammonium salt of phosphorous acid are preferred, and phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, ammonium dihydrogen phosphate, or phosphorous acid, sodium phosphite are more preferred.
[0110] The amount of compound A added to the fiber raw material is not particularly limited, but for example, when the amount of compound A added is converted into the amount of phosphorus atoms, the amount of phosphorus atoms added to the fiber raw material (bone dry mass) is preferably 0.5% by mass or more and 100% by mass or less, more preferably 1% by mass or more and 50% by mass or less, and even more preferably 2% by mass or more and 30% by mass or less. By setting the amount of phosphorus atoms added to the fiber raw material within the above range, the yield of fine fibrous cellulose can be further improved. On the other hand, by setting the amount of phosphorus atoms added to the fiber raw material to the above upper limit or less, a balance between the effect of improving the yield and the cost can be achieved.
[0111] As described above, the compound B used in this embodiment is at least one selected from urea and its derivatives. Examples of the compound B include urea, biuret, 1-phenylurea, 1-benzylurea, 1-methylurea, and 1-ethylurea. From the viewpoint of improving the uniformity of the reaction, it is preferable to use an aqueous solution of compound B. Also, from the viewpoint of further improving the uniformity of the reaction, it is preferable to use an aqueous solution in which both compound A and compound B are dissolved.
[0112] The amount of compound B added relative to the fiber raw material (bone dry mass) is not particularly limited, but is preferably, for example, 1 mass% or more and 500 mass% or less, more preferably 10 mass% or more and 400 mass% or less, and even more preferably 100 mass% or more and 350 mass% or less.
[0113] In the reaction of a fiber raw material containing cellulose with compound A, in addition to compound B, for example, amides or amines may be included in the reaction system. Examples of amides include formamide, dimethylformamide, acetamide, and dimethylacetamide. Examples of amines include methylamine, ethylamine, trimethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, pyridine, ethylenediamine, and hexamethylenediamine. Among these, triethylamine in particular is known to act as a good reaction catalyst.
[0114] In the phosphorus oxo acid group introduction step, it is preferable to add or mix compound A and compound B to the fiber raw material, and then heat-treat the fiber raw material. It is preferable to select a temperature for the heat treatment that can efficiently introduce the phosphorus oxo acid group while suppressing thermal decomposition and hydrolysis of the fiber. The heat treatment temperature is, for example, preferably 50°C to 300°C, more preferably 100°C to 250°C, and even more preferably 130°C to 200°C. In addition, for the heat treatment, various devices having a heat medium can be used, such as a hot air dryer, a stirring dryer, a rotary dryer, a disk dryer, a roll-type heater, a plate-type heater, a fluidized bed dryer, a band-type dryer, a filtration dryer, a vibration fluidized dryer, an airflow dryer, a reduced pressure dryer, an infrared heater, a far-infrared heater, a microwave heater, or a high-frequency dryer.
[0115] In the heat treatment according to the present embodiment, for example, a method of adding compound A to a thin sheet-like fiber raw material by a method such as impregnation, followed by heating, or a method of heating while kneading or stirring the fiber raw material and compound A in a kneader or the like, can be adopted. This makes it possible to suppress unevenness in the concentration of compound A in the fiber raw material and introduce phosphorus oxoacid groups more uniformly onto the surface of the cellulose fibers contained in the fiber raw material. This is believed to be due to the fact that when water molecules move to the surface of the fiber raw material as it dries, the dissolved compound A can be prevented from being attracted to the water molecules by surface tension and moving to the surface of the fiber raw material in the same manner (i.e., causing unevenness in the concentration of compound A).
[0116] In addition, the heating device used in the heat treatment is preferably a device that can constantly discharge, for example, the moisture held by the slurry and the moisture generated in the dehydration condensation (phosphorylation) reaction between compound A and hydroxyl groups contained in cellulose or the like in the fiber raw material, outside the device system. Examples of such heating devices include ovens that use a blowing system. By constantly discharging the moisture within the device system, it is possible to suppress the hydrolysis reaction of phosphate ester bonds, which is the reverse reaction of phosphate esterification, and also to suppress acid hydrolysis of the sugar chains in the fibers. This makes it possible to obtain fine fibrous cellulose with a high axial ratio.
[0117] The time for the heat treatment is, for example, preferably from 1 second to 300 minutes after the moisture is substantially removed from the fiber raw material, more preferably from 1 second to 1000 seconds, and even more preferably from 10 seconds to 800 seconds. In this embodiment, the introduction amount of phosphorus oxo acid groups can be kept within a preferred range by setting the heating temperature and heating time within appropriate ranges.
[0118] The phosphorus oxo acid group introduction step may be carried out at least once, but may also be carried out twice or more. By carrying out the phosphorus oxo acid group introduction step twice or more, a large number of phosphorus oxo acid groups can be introduced into the fiber raw material.
[0119] The amount of phosphorus oxoacid groups introduced in the phosphorus oxoacid group introduction step is preferably 0.60 mmol / g or more, more preferably 0.70 mmol / g or more, even more preferably 0.80 mmol / g or more, even more preferably 1.00 mmol / g or more, and particularly preferably 1.20 mmol / g or more per 1 g (mass) of fiber raw material. The amount of phosphorus oxoacid groups introduced is preferably 5.20 mmol / g or less, more preferably 3.65 mmol / g or less, and even more preferably 3.00 mmol / g or less per 1 g (mass) of fiber raw material. The fact that the amount of phosphorus oxoacid groups introduced in the phosphorus oxoacid group introduction step is within the above range means that the amount of substituents introduced into the fine fibrous cellulose provided in step (A) is within the above range. By setting the amount of phosphorus oxoacid groups introduced within the above range, the amount of substituents introduced into the fine fibrous cellulose provided in step (A) can be set within the above range, and as a result, it becomes easier to produce fine fibrous cellulose having a final fiber width of 10 nm or less. In addition, the transparency of the dispersion or sheet containing the fine fibrous cellulose of the present invention can be more effectively improved.
[0120] <Sulfonic group (sulfur oxoacid group) introduction process> The process for producing fine fibrous cellulose in step (A) may include a sulfonic group introduction step as an anionic group introduction step, in which hydroxyl groups in a fiber raw material containing cellulose react with sulfonic acid to obtain cellulose fibers having sulfonic groups (sulfonic group-introduced fibers).
[0121] In the sulfonic group introduction step, instead of the compound A in the above-mentioned <phosphorus oxo acid group introduction step>, at least one compound (hereinafter also referred to as "compound C") selected from compounds capable of introducing a sulfonic group by reacting with a hydroxyl group possessed by a fiber raw material containing cellulose is used. Compound C may be any compound having a sulfur atom and capable of forming an ester bond with cellulose, and may include, but is not limited to, sulfuric acid or a salt thereof, sulfurous acid or a salt thereof, and sulfuric acid amide. As the sulfuric acid, those of various purities may be used, for example, 96% sulfuric acid (concentrated sulfuric acid). As the sulfurous acid, 5% sulfurous acid water may be used. As the sulfate or sulfite, lithium salt, sodium salt, potassium salt, ammonium salt, and the like of sulfate or sulfite may be used, and these may be neutralized to various degrees. As the sulfuric acid amide, sulfamic acid or the like may be used. In the sulfonic group introduction step, it is preferable to use compound B in the above-mentioned <phosphorus oxo acid group introduction step> in the same manner.
[0122] In the sulfonic group introduction step, it is preferable to mix the cellulose raw material with an aqueous solution containing sulfonic acid and urea and / or a urea derivative, and then heat-treat the cellulose raw material. It is preferable to select a temperature for the heat treatment that allows efficient introduction of sulfonic groups while suppressing thermal decomposition and hydrolysis of the fiber. The heat treatment temperature is preferably 100°C or higher, more preferably 120°C or higher, and even more preferably 150°C or higher. In addition, the heat treatment temperature is preferably 300°C or lower, more preferably 250°C or lower, and even more preferably 200°C or lower.
[0123] In the heat treatment step, it is preferable to heat until substantially no moisture is present. For this reason, the heat treatment time varies depending on the amount of moisture contained in the cellulose raw material and the amount of the aqueous solution containing sulfonic acid and urea and / or a urea derivative added, but is preferably, for example, 10 seconds or more and 10,000 seconds or less. For the heat treatment, various devices having a heat medium can be used, such as a hot air dryer, a stirring dryer, a rotary dryer, a disk dryer, a roll type heater, a plate type heater, a fluidized bed dryer, a band type dryer, a filtration dryer, a vibration fluidized dryer, an airflow dryer, a reduced pressure dryer, an infrared heater, a far infrared heater, a microwave heater, and a high frequency dryer.
[0124] The amount of sulfonic groups introduced in the sulfonic group introduction step is preferably 0.60 mmol / g or more per 1 g (mass) of fiber raw material, more preferably 0.70 mmol / g or more, even more preferably 0.80 mmol / g or more, even more preferably 1.00 mmol / g or more, and particularly preferably 1.20 mmol / g or more. The amount of sulfonic groups introduced is preferably 5.00 mmol / g or less per 1 g (mass) of fiber raw material, more preferably 3.00 mmol / g or less. The amount of sulfonic groups introduced in the sulfonic group introduction step within the above range means that the amount of substituents introduced into the fine fibrous cellulose provided in step (A) is within the above range. By setting the amount of sulfonic groups introduced within the above range, the amount of substituents introduced into the fine fibrous cellulose provided in step (A) can be set within the above range, and as a result, fine fibrous cellulose having a fiber width of 10 nm or less can be easily produced. In addition, the transparency of the dispersion or sheet containing the fine fibrous cellulose of the present invention can be more effectively increased.
[0125] <Xanthate group introduction process> The manufacturing process of the fine fibrous cellulose subjected to the step (A) may include a xanthate group introduction step as an anionic group introduction step. In the xanthate group introduction step, a hydroxyl group of a fiber raw material containing cellulose is replaced with a xanthate group represented by the following formula (2), thereby obtaining a cellulose fiber having a xanthate group (xanthate group-introduced fiber). -OCSS - M + ……(2) Here, M + is at least one selected from the group consisting of a hydrogen ion, a monovalent metal ion, an ammonium ion, and an aliphatic or aromatic ammonium ion.
[0126] In the xanthate group introduction step, first, the fiber raw material containing the cellulose is treated with an alkali solution to obtain alkali cellulose. Examples of the alkali solution include an alkali metal hydroxide aqueous solution and an alkaline earth metal hydroxide aqueous solution. Among them, the alkali solution is preferably an alkali metal hydroxide aqueous solution such as sodium hydroxide or potassium hydroxide, and is particularly preferably an aqueous sodium hydroxide solution. When the alkali solution is an alkali metal hydroxide aqueous solution, the alkali metal hydroxide concentration in the alkali metal hydroxide aqueous solution is preferably 4% by mass or more, more preferably 5% by mass or more. In addition, the alkali metal hydroxide concentration in the alkali metal hydroxide aqueous solution is preferably 9% by mass or less. By setting the alkali metal hydroxide concentration to the above lower limit value or more, the mercerization of cellulose can be sufficiently promoted, the amount of by-products generated during the subsequent xanthation can be reduced, and as a result, the yield of xanthate group-introduced fibers can be increased. This makes it possible to more effectively perform the defibration treatment described below. Furthermore, by setting the alkali metal hydroxide concentration to the above upper limit or less, it is possible to prevent the aqueous alkali metal hydroxide solution from penetrating into the crystalline regions of cellulose while allowing mercerization to proceed, which makes it easier to maintain the cellulose type I crystal structure and further increases the yield of fine fibrous cellulose.
[0127] The alkali treatment time is preferably 30 minutes or more, more preferably 1 hour or more. The alkali treatment time is preferably 6 hours or less, more preferably 5 hours or less. By setting the alkali treatment time within the above range, the final yield can be increased, and the productivity can be improved.
[0128] The alkali cellulose obtained by the above-mentioned alkali treatment is preferably subjected to solid-liquid separation to remove as much aqueous solution as possible. This can reduce the water content during the subsequent xanthate treatment, and can promote the reaction. As a method for solid-liquid separation, for example, a general dehydration method such as centrifugation or filtration can be used. In addition, the concentration of alkali metal hydroxide contained in the alkali cellulose after solid-liquid separation is preferably 3% by mass or more and 8% by mass or less with respect to the total mass of the alkali cellulose after solid-liquid separation.
[0129] In the xanthate group introduction process, a xanthate formation process is carried out after the alkali treatment. In the xanthate formation process, carbon disulfide (CS2) is reacted with alkali cellulose to form (-O - Na + ) group to (-OCSS - Na + In the above, the metal ions introduced into the alkali cellulose are typically Na + However, similar reactions occur with other alkali metal ions.
[0130] In the xanthate treatment, it is preferable to supply 10% by mass or more of carbon disulfide based on the absolute dry mass of cellulose in the alkali cellulose. In addition, in the xanthate treatment, the time for which carbon disulfide and alkali cellulose are in contact is preferably 30 minutes or more, more preferably 1 hour or more. Although the xanthate formation proceeds quickly when carbon disulfide contacts alkali cellulose, it takes time for carbon disulfide to penetrate into the inside of alkali cellulose, so it is preferable to set the reaction time to the above range. On the other hand, the time for which carbon disulfide contacts alkali cellulose may be 6 hours or less, which allows sufficient penetration into the mass of alkali cellulose after dehydration, and allows the reaction-ready xanthate formation to be almost completed.
[0131] The reaction temperature in the xanthate treatment is preferably 46° C. or less. By setting the reaction temperature within the above range, it is easy to suppress the decomposition of the alkali cellulose. In addition, by setting the reaction temperature within the above range, it is easy to react uniformly, so that the generation of by-products can be suppressed, and further, the removal of the generated xanthate group can be suppressed.
[0132] The amount of xanthate group introduced in the xanthate group introduction step is preferably 0.60 mmol / g or more per 1 g (mass) of fiber raw material, more preferably 0.70 mmol / g or more, even more preferably 0.80 mmol / g or more, even more preferably 1.00 mmol / g or more, and particularly preferably 1.20 mmol / g or more. In addition, the amount of xanthate group introduced is preferably 5.00 mmol / g or less per 1 g (mass) of fiber raw material, and more preferably 3.00 mmol / g or less. In addition, the amount of xanthate group introduced in the xanthate group introduction step being within the above range means that the amount of substituent introduction of the fine fibrous cellulose provided in step (A) is within the above range. By setting the amount of xanthate group introduction within the above range, the amount of substituent introduction of the fine fibrous cellulose provided in step (A) can be set within the above range, and as a result, it becomes easier to produce fine fibrous cellulose having a fiber width of 10 nm or less. In addition, the transparency of the dispersion or sheet containing the fine fibrous cellulose of the present invention can be more effectively increased.
[0133] <Cleaning process> In the production process of the fine fibrous cellulose to be subjected to step (A), a washing step can be carried out on the anionic group-introduced fiber, if necessary. The washing step is carried out, for example, by washing the anionic group-introduced fiber with water or an organic solvent. The washing step may be carried out after each step described below, and the number of washing steps carried out in each washing step is not particularly limited.
[0134] <Alkaline treatment process> In the production process of the fine fibrous cellulose to be subjected to step (A), an alkali treatment may be carried out on the fiber raw material between the anionic group introduction step and the defibration step described below. The alkali treatment method is not particularly limited, but may be, for example, a method of immersing the anionic group-introduced fiber in an alkali solution.
[0135] The alkaline compound contained in the alkaline solution is not particularly limited, and may be an inorganic alkaline compound or an organic alkaline compound. In this embodiment, it is preferable to use, for example, sodium hydroxide or potassium hydroxide as the alkaline compound because of its high versatility. The solvent contained in the alkaline solution may be either water or an organic solvent. Among them, the solvent contained in the alkaline solution is preferably a polar solvent including water or a polar organic solvent exemplified by alcohol, and more preferably an aqueous solvent including at least water. As the alkaline solution, for example, an aqueous sodium hydroxide solution or an aqueous potassium hydroxide solution is preferable because of its high versatility.
[0136] The temperature of the alkaline solution in the alkaline treatment step is not particularly limited, but is preferably, for example, from 5° C. to 80° C., and more preferably from 10° C. to 60° C. The immersion time of the anionic group-introduced fiber in the alkaline solution in the alkaline treatment step is not particularly limited, but is, for example, preferably from 5 minutes to 30 minutes, and more preferably from 10 minutes to 20 minutes. The amount of the alkaline solution used in the alkaline treatment is not particularly limited, but is, for example, preferably from 100 mass% to 100,000 mass%, and more preferably from 1,000 mass% to 10,000 mass%, based on the absolute dry mass of the anionic group-introduced fiber.
[0137] In order to reduce the amount of alkaline solution used in the alkaline treatment step, the anionic group-introduced fiber may be washed with water or an organic solvent after the anionic group-introducing step and before the alkaline treatment step. From the viewpoint of improving handleability, it is preferable to wash the alkaline-treated anionic group-introduced fiber with water or an organic solvent after the alkaline treatment step and before the defibration treatment step.
[0138] <Acid treatment process> In the production process of the fine fibrous cellulose subjected to step (A), the fiber raw material may be subjected to an acid treatment between the step of introducing anionic groups and the defibration treatment step described below. For example, the anionic group introduction step, acid treatment, alkali treatment, and defibration treatment may be performed in this order.
[0139] The method of acid treatment is not particularly limited, but may be, for example, a method of immersing the fiber raw material in an acidic solution containing an acid. The concentration of the acidic solution used is not particularly limited, but is preferably, for example, 10% by mass or less, and more preferably, 5% by mass or less. The pH of the acidic solution used is not particularly limited, but is preferably, for example, 0 to 4, and more preferably, 1 to 3. The acid contained in the acidic solution may be, for example, an inorganic acid, a sulfonic acid, a carboxylic acid, or the like. Examples of inorganic acids include sulfuric acid, nitric acid, hydrobromic acid, hydroiodic acid, hypochlorous acid, chlorous acid, chloric acid, perchloric acid, phosphoric acid, and boric acid. Examples of sulfonic acids include, for example, methanesulfonic acid, ethanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid. Examples of carboxylic acids include, for example, formic acid, acetic acid, citric acid, gluconic acid, lactic acid, oxalic acid, and tartaric acid. Among these, it is particularly preferable to use hydrochloric acid or sulfuric acid.
[0140] The temperature of the acid solution in the acid treatment is not particularly limited, but is preferably, for example, from 5° C. to 100° C., and more preferably from 20° C. to 90° C. The immersion time in the acid solution in the acid treatment is not particularly limited, but is, for example, preferably from 5 minutes to 120 minutes, and more preferably from 10 minutes to 60 minutes. The amount of the acid solution used in the acid treatment is not particularly limited, but is, for example, preferably from 100 mass% to 100,000 mass%, and more preferably from 1,000 mass% to 10,000 mass%, based on the absolute dry mass of the fiber raw material.
[0141] <Nitrogen removal treatment> The production process of fine fibrous cellulose subjected to step (A) may further include a step of reducing the amount of nitrogen introduced into the fibrous cellulose or the amount of nitrogen present in the system (nitrogen removal treatment step). By reducing the amount of nitrogen, fine fibrous cellulose capable of further suppressing coloration can be obtained. The nitrogen removal treatment step may be performed after the uniform dispersion treatment step in step (B) described later, but is preferably performed before the uniform dispersion treatment step in step (B) described later. In addition, it is preferably performed before the defibration treatment step in step (A) described later.
[0142] In the nitrogen removal treatment step, it is preferable to adjust the pH of the slurry containing the anionic group-introduced fiber to 10 or more and to perform a heat treatment. In the heat treatment, the liquid temperature of the slurry is preferably 50° C. or more and 100° C. or less, and the heating time is preferably 15 minutes or more and 180 minutes or less. When adjusting the pH of the slurry containing the anionic group-introduced fiber, it is preferable to add an alkali compound that can be used in the above-mentioned alkali treatment step to the slurry.
[0143] After the nitrogen removal treatment step, the anionic group-introduced fiber may be subjected to a washing step, if necessary. The washing step is carried out by washing the anionic group-introduced fiber with, for example, water or an organic solvent. The number of washing steps carried out in each washing step is not particularly limited.
[0144] <Defibrillation processing> The manufacturing process of the fine fibrous cellulose subjected to step (A) includes a defibration treatment step. This produces fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less. In the defibration treatment step, for example, a defibration treatment device can be used. The defibration treatment device is not particularly limited, but for example, a high-speed defibrator, a grinder (stone mill type grinder), a high-pressure homogenizer or an ultra-high-pressure homogenizer, a high-pressure collision type grinder, a ball mill, a bead mill, a disk type refiner, a conical refiner, a biaxial kneader, a vibration mill, a homomixer under high-speed rotation, an ultrasonic disperser, or a beater can be used. Among the above defibration treatment devices, it is more preferable to use a high-speed defibrator, a high-pressure homogenizer, or an ultra-high-pressure homogenizer, which are less affected by the grinding media and have less risk of contamination.
[0145] The treatment conditions in the fiberization process are not particularly limited, but for example, when a high-pressure homogenizer is used, the pressure during treatment is preferably 1 MPa or more and 350 MPa or less, more preferably 10 MPa or more and 300 MPa or less, and even more preferably 50 MPa or more and 250 MPa or less.
[0146] In the defibration process, for example, it is preferable to dilute the anionic group-introduced fiber with a dispersion medium to make it into a slurry state. As the dispersion medium, one or more selected from water and organic solvents such as polar organic solvents can be used. The polar organic solvent is not particularly limited, but for example, alcohols, polyhydric alcohols, ketones, ethers, esters, aprotic polar solvents, etc. are preferable. Examples of alcohols include methanol, ethanol, isopropanol, n-butanol, isobutyl alcohol, etc. Examples of polyhydric alcohols include ethylene glycol, propylene glycol, glycerin, etc. Examples of ketones include acetone, methyl ethyl ketone (MEK), etc. Examples of ethers include diethyl ether, tetrahydrofuran, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol mono n-butyl ether, propylene glycol monomethyl ether, etc. Examples of esters include ethyl acetate, butyl acetate, etc. Aprotic polar solvents include dimethylsulfoxide (DMSO), dimethylformamide (DMF), dimethylacetamide (DMAc), and N-methyl-2-pyrrolidinone (NMP).
[0147] The solid content concentration of the fine fibrous cellulose during the defibration treatment can be appropriately set. In addition, the slurry obtained by dispersing the anionic group-introduced fibers in a dispersion medium may contain solid contents other than the anionic group-introduced fibers, such as urea having hydrogen bonding properties.
[0148] The fiber width of the fine fibrous cellulose after defibration treatment in step (A) is preferably from 1 to 50 nm, more preferably from 1 to 25 nm, further preferably from 1 to 15 nm, and particularly preferably from 1 to 10 nm.
[0149] In addition, when the fine fibrous cellulose to be subjected to step (A) is made into an aqueous dispersion with a concentration of 0.1% by mass, and the nanofiber yield is calculated, the nanofiber yield is preferably 90% by mass or more, more preferably 93% by mass or more, and even more preferably 96% by mass or more. The nanofiber yield may be 100% by mass. Here, the nanofiber yield is a value measured based on the cellulose concentration of the supernatant obtained by centrifuging a fine fibrous cellulose dispersion with a concentration of 0.1% by mass using a refrigerated high-speed centrifuge (Kokusan Co., Ltd., H-2000B) at 12,000G for 10 minutes, according to the following formula. Nanofiber yield (mass%) = cellulose concentration in supernatant (mass%) / 0.1 × 100
[0150] Furthermore, when the fine fibrous cellulose to be subjected to step (A) is made into an aqueous dispersion with a concentration of 0.2% by mass, the haze of the aqueous dispersion is preferably 10% or less, more preferably 5.0% or less, and even more preferably 3.0% or less. The haze of the aqueous dispersion may be 0%. Here, the haze of the aqueous dispersion of fine fibrous cellulose is a value measured in accordance with JIS K 7136:2000 using a haze meter (Murakami Color Research Laboratory, HM-150). When measuring, a glass cell for liquids with an optical path length of 1 cm (Fujiwara Manufacturing, MG-40, reverse optical path) is used. The zero point measurement is performed with ion-exchanged water placed in the glass cell, and the dispersion to be measured is left to stand for 24 hours in an environment of 23°C and relative humidity 50% before measurement, and the liquid temperature of the dispersion is set to 23°C.
[0151] By controlling the fiber width of the fine fibrous cellulose subjected to step (A) and the nanofiber yield and haze of the fine fibrous cellulose dispersion within the above ranges, it is possible to more effectively improve the transparency when the fine fibrous cellulose obtained via step (B) is made into a slurry or sheet.
[0152] <Substituent removal treatment> The method for producing fine fibrous cellulose of the present invention includes a step (A) of removing at least a part of the substituents from fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less. In this specification, the step of removing at least a part of the substituents from the fine fibrous cellulose is also referred to as a substituent removal treatment step.
[0153] Examples of the substituent removal treatment step include a step of heat treating, enzyme treating, acid treating, alkali treating, etc., fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less. These may be performed alone or in combination. Among them, the substituent removal treatment step is preferably a heat treating step or an enzyme treating step. By passing through the above treatment steps, at least a part of the substituents is removed from the fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less, and fine fibrous cellulose having an introduction amount of less than 0.5 mmol / g can be obtained.
[0154] The substituent removal treatment step is preferably carried out in the form of a slurry. That is, the substituent removal treatment step is preferably a step of subjecting a slurry containing a fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less to a heat treatment, an enzyme treatment, an acid treatment, an alkali treatment, or the like. By carrying out the substituent removal treatment step in the form of a slurry, it is possible to prevent colored substances generated by heating or the like during the substituent removal treatment, and the residue of added or generated acids, alkalis, salts, and the like. This makes it possible to suppress coloration when the fine fibrous cellulose obtained through step (B) is made into a slurry or sheet. In addition, when a treatment is carried out to remove salts derived from the substituents removed after the substituent removal treatment, it is also possible to increase the efficiency of salt removal.
[0155] When a substitution removal treatment is performed on a slurry containing a fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less, the concentration of the fine fibrous cellulose in the slurry is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.2% by mass or more. The concentration of the fine fibrous cellulose in the slurry is preferably 20% by mass or less, more preferably 15% by mass or less, and even more preferably 10% by mass or less. By setting the concentration of the fine fibrous cellulose in the slurry within the above range, the substitution removal treatment can be performed more efficiently. Furthermore, by setting the concentration of the fine fibrous cellulose in the slurry within the above range, it is possible to prevent the residue of colored substances generated by heating or the like during the substitution removal treatment, and acids, alkalis, salts, etc. that are added or generated. This makes it possible to suppress coloring when the fine fibrous cellulose obtained through step (B) is made into a slurry or sheet. In addition, when a treatment is performed to remove salts derived from the substituents removed after the substitution removal treatment, it is also possible to increase the efficiency of salt removal.
[0156] When the substituent removal treatment step is a step of heat treating fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less, the heating temperature in the heat treatment step is preferably 40° C. or more, more preferably 50° C. or more, and even more preferably 60° C. or more. The heating temperature in the heat treatment step is preferably 250° C. or less, more preferably 230° C. or less, and even more preferably 200° C. or less. In particular, when the substituent of the fine fibrous cellulose to be subjected to the substituent removal treatment step is a phosphorus oxo acid group or a sulfone group, the heating temperature in the heat treatment step is preferably 80° C. or more, more preferably 100° C. or more, and even more preferably 120° C. or more.
[0157] When the substituent removal treatment step is a step of heat treatment, the heating device that can be used in the heat treatment step is not particularly limited, but a hot air heating device, a steam heating device, an electric heating device, a hydrothermal heating device, a thermal heating device, an infrared heating device, a far-infrared heating device, a microwave heating device, a high-frequency heating device, a stirring dryer, a rotary dryer, a disk dryer, a roll-type heating device, a plate-type heating device, a fluidized bed dryer, a band-type dryer, a filtration dryer, a vibration fluidized dryer, an airflow dryer, and a reduced pressure dryer can be used. From the viewpoint of preventing evaporation, it is preferable that the heating is performed in a closed system, and from the viewpoint of further increasing the heating temperature, it is preferable that the heating is performed in a pressure-resistant device or container. The heating treatment may be a batch treatment, a batch continuous treatment, or a continuous treatment.
[0158] When the substituent removal treatment step is a step of enzymatically treating fine fibrous cellulose having substituents and a fiber width of 1000 nm or less, it is preferable to use a phosphate ester hydrolase, a sulfate ester hydrolase, or the like in the enzymatic treatment step.
[0159] In the enzyme treatment step, the enzyme is preferably added so that the enzyme activity is 0.1 nkat or more per 1 g of fine fibrous cellulose, more preferably 1.0 nkat or more, and even more preferably 10 nkat or more. The enzyme is preferably added so that the enzyme activity is 100,000 nkat or less per 1 g of fine fibrous cellulose, more preferably 50,000 nkat or less, and even more preferably 10,000 nkat or less. After adding the enzyme to the fine fibrous cellulose dispersion (slurry), it is preferable to perform a treatment under conditions of 0°C or more and less than 50°C for 1 minute to 100 hours.
[0160] After the enzyme reaction, a step of inactivating the enzyme may be performed. Examples of the method of inactivating the enzyme include a method of inactivating the enzyme by adding an acid component or an alkali component to the slurry that has been subjected to the enzyme treatment, and a method of inactivating the enzyme by raising the temperature of the slurry that has been subjected to the enzyme treatment to 90° C. or higher.
[0161] When the substituent removal treatment step is a step of acid-treating fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less, it is preferable to add an acid compound that can be used in the acid treatment step described above to the slurry in the acid treatment step.
[0162] When the substituent removal treatment step is a step of subjecting fine fibrous cellulose having a substituent and having a fiber width of 1000 nm or less to an alkali treatment, it is preferable to add an alkali compound that can be used in the alkali treatment step described above to the slurry in the alkali treatment step.
[0163] In the substituent removal treatment step, it is preferable that the substituent removal reaction proceeds uniformly. In order to proceed with the reaction uniformly, for example, the slurry containing the fine fibrous cellulose may be stirred, or the specific surface area of the slurry may be increased. As a method for stirring the slurry, an external mechanical shear may be applied, or the self-stirring may be promoted by increasing the liquid feed rate of the slurry during the reaction.
[0164] In the substituent removal treatment step, a spacer molecule may be added. The spacer molecule enters between adjacent fine fibrous cellulose particles, thereby acting as a spacer for providing a fine space between the fine fibrous cellulose particles. By adding such a spacer molecule in the substituent removal treatment step, aggregation of the fine fibrous cellulose after the substituent removal treatment can be suppressed. This makes it possible to more effectively increase the transparency of the dispersion or sheet containing the fine fibrous cellulose.
[0165] The spacer molecule is preferably a water-soluble organic compound. Examples of the water-soluble organic compound include sugars, water-soluble polymers, urea, and the like. Specifically, trehalose, urea, polyethylene glycol (PEG), polyethylene oxide (PEO), carboxymethyl cellulose, polyvinyl alcohol (PVA), and the like can be mentioned. Further, as the water-soluble organic compound, alkyl methacrylate-acrylic acid copolymer, polyvinylpyrrolidone, sodium polyacrylate, propylene glycol, dipropylene glycol, polypropylene glycol, isoprene glycol, hexylene glycol, 1,3-butylene glycol, polyacrylamide, xanthan gum, guar gum, tamarind gum, carrageenan, locust bean gum, quince seed, alginic acid, pullulan, carrageenan, pectin, cationized starch, raw starch, oxidized starch, etherified starch, esterified starch, amylose and other starches, glycerin, diglycerin, polyglycerin, hyaluronic acid, and metal salts of hyaluronic acid can also be used.
[0166] Also, known pigments can be used as the spacer molecule. For example, kaolin (including clay), calcium carbonate, titanium oxide, zinc oxide, amorphous silica (including colloidal silica), aluminum oxide, zeolite, sepiolite, smectite, synthetic smectite, magnesium silicate, magnesium carbonate, magnesium oxide, diatomaceous earth, styrene-based plastic pigment, hydrotalcite, urea resin-based plastic pigment, benzoguanamine-based plastic pigment, and the like can be mentioned.
[0167] <pH adjustment step> When the substituent removal treatment step is performed in a slurry state, a step of adjusting the pH of the slurry containing microfibrillar cellulose may be provided before the substituent removal treatment step. For example, an anionic group is introduced into the cellulose fiber, and the counter ion of this anionic group is Na +In this case, the slurry containing the defibrated fine fibrous cellulose exhibits weak alkalinity. When heating is performed in this state, monosaccharides, which are one of the causes of coloring, may be generated due to decomposition of the cellulose, so the pH of the slurry is preferably adjusted to 8 or less, and more preferably adjusted to 6 or less. Similarly, monosaccharides may be generated under acidic conditions, so the pH of the slurry is preferably adjusted to 3 or more, and more preferably adjusted to 4 or more.
[0168] In addition, when the fine fibrous cellulose having a substituent is a fine fibrous cellulose having a phosphate group, from the viewpoint of improving the efficiency of removing the substituent, it is preferable that the phosphorus of the phosphate group is in a state that is easily susceptible to nucleophilic attack. The phosphorus that is easily susceptible to nucleophilic attack is cellulose-OP(=O)(-OH + )(-O-Na + To achieve this state, the pH of the slurry is preferably adjusted to 3 or more and 8 or less, and more preferably adjusted to 4 or more and 6 or less.
[0169] The means for adjusting the pH is not particularly limited, and for example, an acid component or an alkali component may be added to the slurry containing the fine fibrous cellulose. The acid component may be either an inorganic acid or an organic acid, and examples of the inorganic acid include sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid. Examples of the organic acid include formic acid, acetic acid, citric acid, malic acid, lactic acid, adipic acid, sebacic acid, stearic acid, maleic acid, succinic acid, tartaric acid, fumaric acid, and gluconic acid. The alkali component may be an inorganic alkali compound or an organic alkali compound. Examples of the inorganic alkali compound include lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium carbonate, lithium hydrogen carbonate, potassium carbonate, potassium hydrogen carbonate, sodium carbonate, and sodium hydrogen carbonate. Examples of the organic alkali compound include ammonia, hydrazine, methylamine, ethylamine, diethylamine, triethylamine, propylamine, dipropylamine, butylamine, diaminoethane, diaminopropane, diaminobutane, diaminopentane, diaminohexane, cyclohexylamine, aniline, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, benzyltrimethylammonium hydroxide, pyridine, and N,N-dimethyl-4-aminopyridine.
[0170] In addition, in the pH adjustment step, an ion exchange treatment may be performed to adjust the pH. In the ion exchange treatment, a strong acid cation exchange resin or a weak acid ion exchange resin may be used. By treating with an appropriate amount of cation exchange resin for a sufficient time, a slurry containing fine fibrous cellulose with a desired pH can be obtained. Furthermore, in the pH adjustment step, the addition of an acid component or an alkali component may be combined with the ion exchange treatment.
[0171] <Salt removal process> After the substituent removal treatment step, it is preferable to perform a treatment for removing salts derived from the removed substituents. By removing the salts derived from the substituents, it becomes easier to obtain fine fibrous cellulose capable of suppressing coloration. The means for removing the salts derived from the substituents is not particularly limited, and examples thereof include a washing treatment. The washing treatment is performed by washing the fine fibrous cellulose aggregated in the substituent removal treatment with, for example, water or an organic solvent. From the viewpoint of more effectively suppressing yellowing, the washing treatment is preferably performed by filtration dehydration, centrifugal dehydration, or centrifugation.
[0172] (Process (B)) The method for producing fine fibrous cellulose of the present invention includes a step (A) of removing at least a part of the substituents from fine fibrous cellulose having a substituent and a fiber width of 1000 nm or less, and a step (B) of performing a uniform dispersion treatment after the step (A). The uniform dispersion treatment step (B) is a step of uniformly dispersing the fine fibrous cellulose obtained through the substituent removal treatment in the step (A). In the step (A), the fine fibrous cellulose is subjected to a substituent removal treatment, whereby at least a part of the fine fibrous cellulose is aggregated. In the step (B), the state in which the fine fibrous cellulose is uniformly dispersed in the step (B) refers to a state in which the fiber width of the fine fibrous cellulose is 10 nm or less. Thus, the fine fibrous cellulose obtained by the production method of the present invention has a fiber width of 10 nm or less, even though the amount of the introduced substituents is a low amount of less than 0.5 mmol / g.
[0173] In the uniform dispersion treatment step (B), for example, a high-speed defibrator, a grinder (stone mill type grinder), a high-pressure homogenizer, a high-pressure collision type grinder, a ball mill, a bead mill, a disk type refiner, a conical refiner, a twin-screw kneader, a vibration mill, a homomixer under high-speed rotation, an ultrasonic disperser or a beater can be used. Among the above-mentioned uniform dispersion treatment devices, it is more preferable to use a high-speed defibrator or a high-pressure homogenizer.
[0174] The treatment conditions in the uniform dispersion treatment step (B) are not particularly limited, but it is preferable to increase the maximum moving speed of the fine fibrous cellulose during treatment and the pressure during treatment. In the high-speed defibrator, the peripheral speed is preferably 20 m / sec or more, more preferably 25 m / sec or more, and even more preferably 30 m / sec or more. The high-pressure homogenizer is more preferably used because it has a higher maximum moving speed of the fine fibrous cellulose during treatment and a higher pressure during treatment than the high-speed defibrator. In the high-pressure homogenizer treatment, the pressure during treatment is preferably 1 MPa or more, more preferably 10 MPa or more, even more preferably 50 MPa or more, and particularly preferably 100 MPa or more. In the high-pressure homogenizer treatment, the pressure during treatment is preferably 350 MPa or less, more preferably 300 MPa or less, and even more preferably 250 MPa or less.
[0175] In step (B), the above-mentioned spacer molecule may be added. By adding such a spacer molecule in the uniform dispersion treatment step of step (B), the fine fibrous cellulose can be uniformly dispersed more smoothly. This makes it possible to more effectively increase the transparency of the dispersion liquid or sheet containing the fine fibrous cellulose.
[0176] (Method of manufacturing laminated sheet) The method for producing a laminate sheet of the present invention preferably includes a step of forming a fiber layer containing fibrous cellulose having an amount of introduced substituents of less than 0.5 mmol / g and a fiber width of 1 to 10 nm, and a step of coating a resin composition on the fiber layer. The method for producing a laminate sheet of the present invention may also include a step of coating a fine fibrous cellulose dispersion containing fibrous cellulose having an amount of introduced substituents of less than 0.5 mmol / g and a fiber width of 1 to 10 nm on the resin layer.
[0177] When applying a resin composition onto a fiber layer or forming a resin layer, it is preferable to apply a resin composition containing a resin and form a coating film, and then provide a drying step.
[0178] In addition to the above-mentioned methods, the laminate sheet can be produced by placing a resin layer on a fiber layer and hot pressing it. In addition, the fiber layer can be placed in a mold for injection molding, and heated and molten resin can be injected into the mold to bond the resin layer to the fiber layer.
[0179] The step of forming a fiber layer containing fibrous cellulose having an amount of substituent introduction of less than 0.5 mmol / g and a fiber width of 1 to 10 nm preferably includes a step of coating a fine fibrous cellulose dispersion (slurry containing fine fibrous cellulose) on a substrate or a step of making a paper from the fine fibrous cellulose dispersion. When a fine fibrous cellulose dispersion containing fibrous cellulose having a fiber width of 1000 nm or less is coated on a resin layer, the substrate may be changed to a resin layer and a coating method described later may be adopted.
[0180] The fine fibrous cellulose dispersion (slurry containing fine fibrous cellulose) may contain any component contained in the fiber layer, and it is preferable that the nanofiber yield, haze, pH, viscosity, free nitrogen amount, etc. of the fine fibrous cellulose dispersion are within the numerical ranges described in the above section on <Fine fibrous cellulose>.
[0181] <Coating process> The process of coating a substrate with a fine fibrous cellulose dispersion (slurry containing fine fibrous cellulose) (hereinafter also referred to as a coating process) is a process of coating a substrate with a fine fibrous cellulose dispersion, drying the substrate, and peeling off the resulting fine fibrous cellulose-containing sheet from the substrate to obtain a sheet. By using a coating device and a long substrate, sheets can be produced continuously. The concentration of the fine fibrous cellulose dispersion to be coated is not particularly limited, but is preferably 0.05% by mass or more and 5% by mass or less.
[0182] The quality of the substrate used in the coating process is not particularly limited, but a substrate with high wettability to the fine fibrous cellulose dispersion liquid is better in that it can suppress the shrinkage of the sheet during drying, but it is preferable to select a substrate from which the sheet formed after drying can be easily peeled off. Among them, a resin plate or a metal plate is preferable, but is not particularly limited. For example, resin plates such as acrylic plates, polyethylene terephthalate plates, vinyl chloride plates, polystyrene plates, and polyvinylidene chloride plates, metal plates such as aluminum plates, zinc plates, copper plates, and iron plates, and those whose surfaces have been oxidized, stainless steel plates, brass plates, etc. can be used.
[0183] In the coating process, when the viscosity of the fine fibrous cellulose dispersion is low and it spreads on the substrate, a damming frame may be fixed on the substrate to obtain a fine fibrous cellulose-containing sheet of a predetermined thickness and basis weight. The quality of the damming frame is not particularly limited, but it is preferable to select one that allows the end of the sheet to be easily peeled off after drying. Among them, a resin plate or a metal plate is preferable, but is not particularly limited. For example, resin plates such as acrylic plates, polyethylene terephthalate plates, vinyl chloride plates, polystyrene plates, and polyvinylidene chloride plates, metal plates such as aluminum plates, zinc plates, copper plates, and iron plates, and those whose surfaces have been oxidized, stainless steel plates, brass plates, and the like can be used.
[0184] Examples of the coater that can be used to coat the fine fibrous cellulose dispersion include a bar coater, a roll coater, a gravure coater, a die coater, a curtain coater, and an air doctor coater. The bar coater, die coater, curtain coater, and spray coater are preferred because they can achieve a more uniform thickness.
[0185] The coating temperature is not particularly limited, but is preferably from 20° C. to 45° C. When the coating temperature is equal to or higher than the lower limit, the fine fibrous cellulose dispersion can be easily coated, and when the coating temperature is equal to or lower than the upper limit, volatilization of the dispersion medium during coating can be suppressed.
[0186] In the coating process, the finished sheet weight is 10 g / m 2 More than 100g / m 2 It is preferable to coat the fine fibrous cellulose dispersion so that the basis weight falls within the above range. By coating so that the basis weight falls within the above range, a fiber layer having excellent strength can be obtained.
[0187] The manufacturing process of the fine fibrous cellulose-containing sheet preferably includes a step of drying the fine fibrous cellulose dispersion applied to the substrate. The drying method is not particularly limited, but may be either a non-contact drying method or a method of drying the sheet while restraining the sheet, or a combination of these methods.
[0188] As the non-contact drying method, there is no particular limitation, but a method of drying by heating with hot air, infrared rays, far infrared rays or near infrared rays (heat drying method), and a method of drying by vacuum (vacuum drying method) can be applied. The heat drying method and the vacuum drying method may be combined, but the heat drying method is usually applied. Drying by infrared rays, far infrared rays or near infrared rays can be performed using an infrared device, a far infrared device or a near infrared device, but is not particularly limited. The heating temperature in the heat drying method is not particularly limited, but is preferably 20°C or higher and 150°C or lower, and more preferably 25°C or higher and 105°C or lower. If the heating temperature is set to the above lower limit value or higher, the dispersion medium can be quickly volatilized, and if the heating temperature is set to the above upper limit value or lower, the cost required for heating can be suppressed and the discoloration of the fine fibrous cellulose due to heat can be suppressed.
[0189] After drying, the obtained fine fibrous cellulose-containing sheet is peeled off from the substrate, but when the substrate is a sheet, the fine fibrous cellulose-containing sheet and the substrate may be rolled up while still stacked, and the fine fibrous cellulose-containing sheet may be peeled off from the substrate immediately before use. In this way, a fine fibrous cellulose-containing sheet that will become a fiber layer is obtained.
[0190] In the step of coating the resin composition on the fiber layer, it is preferable to coat the resin composition on the surface of the fine fibrous cellulose-containing sheet that is peeled off from the substrate, thereby making it possible to further increase the interlayer adhesion between the fiber layer and the resin layer.
[0191] <Paper making process> The manufacturing process of the fine fibrous cellulose-containing sheet to be the fiber layer may include a process of making a paper from the fine fibrous cellulose dispersion. Examples of the papermaking machine in the papermaking process include continuous papermaking machines such as Fourdrinier, cylinder, and tilt types, and multi-layer papermaking machines that combine these. In the papermaking process, known papermaking methods such as handmaking may be used.
[0192] In the papermaking process, the fine fibrous cellulose dispersion is filtered and dehydrated on a wire to obtain a sheet in a wet paper state, and then pressed and dried to obtain a sheet. The concentration of the fine fibrous cellulose dispersion is not particularly limited, but is preferably 0.05% by mass or more and 5% by mass or less. When the fine fibrous cellulose dispersion is filtered and dehydrated, the filter cloth used during filtration is not particularly limited, but it is important that the fine fibrous cellulose does not pass through and the filtration speed does not become too slow. Such filter cloth is not particularly limited, but is preferably a sheet, fabric, or porous membrane made of an organic polymer. The organic polymer is not particularly limited, but is preferably a non-cellulose organic polymer such as polyethylene terephthalate, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), etc. Specifically, examples include a porous membrane of polytetrafluoroethylene with a pore size of 0.1 μm to 20 μm, for example, 1 μm, and a woven fabric of polyethylene terephthalate or polyethylene with a pore size of 0.1 μm to 20 μm, for example, 1 μm.
[0193] The method for producing a sheet from a fine fibrous cellulose dispersion is not particularly limited, and examples thereof include a method using a production apparatus described in WO2011 / 013567. This production apparatus includes a water squeezing section in which the fine fibrous cellulose dispersion is discharged onto an endless belt and the dispersion medium is squeezed out of the discharged fine fibrous cellulose dispersion to produce a web, and a drying section in which the web is dried to produce a fiber sheet. An endless belt is disposed between the water squeezing section and the drying section, and the web produced in the water squeezing section is transported to the drying section while still placed on the endless belt.
[0194] The dehydration method usable in the present invention is not particularly limited, but includes dehydration methods commonly used in paper production, and preferably includes a method of dehydrating with a roll press after dehydrating with a fourdrinier, cylinder, inclined wire, etc. Furthermore, the drying method is not particularly limited, but includes a method used in paper production, and preferably includes a method such as a cylinder dryer, Yankee dryer, hot air drying, near-infrared heater, or infrared heater.
[0195] (Laminate) The present invention may also relate to a laminate obtained by laminating the above-mentioned laminate sheet and an adherend. In addition, when the adherend is disposed on the resin layer side of the laminate sheet, the resin layer in the laminate sheet may function as an adhesive layer. Examples of the adherend include an organic film (hereinafter also referred to as an organic layer) and an inorganic film (hereinafter also referred to as an inorganic layer). Among them, the laminate of the present invention is preferably a laminate obtained by laminating the above-mentioned laminate sheet and an organic film. In addition, examples of the organic film include a resin film, a resin plate, and a resin molded body.
[0196] Resin films, resin plates, and resin molded articles (hereinafter simply referred to as resin films) are layers whose main component is a natural resin or a synthetic resin. Here, the main component refers to a component that is contained in an amount of 50% by mass or more relative to the total mass of the resin film. The content of the resin component is preferably 60% by mass or more relative to the total mass of the resin film, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more. The content of the resin component may be 100% by mass relative to the total mass of the resin film.
[0197] Examples of natural resins include rosin-based resins such as rosin, rosin ester, and hydrogenated rosin ester.
[0198] Examples of synthetic resins include polyolefin resins, cyclic olefin resins, polycarbonate resins, polyethylene terephthalate resins, polyethylene naphthalate resins, polyimide resins, polystyrene resins, acrylic resins, etc. Among these, the synthetic resin is preferably a polyolefin resin, and preferably has at least one selected from a polyethylene resin and a polypropylene resin.
[0199] The method for forming the organic layer is not particularly limited, but examples thereof include a coating method, an injection molding method, and a heat and pressure method. In the coating method, it is preferable to coat the resin composition forming the organic layer on the resin layer of the laminated sheet and heat-cure or photo-cure it. In the heat and pressure method, it is preferable to heat-press the resin film in a state where it is superposed on the resin layer of the laminated sheet. The heat press conditions at this time can be appropriately selected with reference to the glass transition temperature of the resin film, etc.
[0200] The material constituting the inorganic layer is not particularly limited, and examples thereof include aluminum, silicon, magnesium, zinc, tin, nickel, titanium; their oxides, carbides, nitrides, oxycarbides, oxynitrides, or oxycarbonitrides; or mixtures thereof. From the viewpoint of stably maintaining high moisture resistance, silicon oxide, silicon nitride, silicon oxide carbide, silicon oxynitride, silicon oxycarbonitride, aluminum oxide, aluminum nitride, aluminum oxide carbide, aluminum oxynitride, or mixtures thereof are preferred.
[0201] The method for forming the inorganic layer is not particularly limited, and examples thereof include chemical vapor deposition (CVD) and physical vapor deposition (PVD). Specific examples of the CVD method include plasma CVD using plasma and catalytic chemical vapor deposition (Cat-CVD) in which a material gas is catalytically decomposed by pyrolysis using a heated catalyst. Specific examples of the PVD method include vacuum deposition, ion plating, and sputtering. In addition, atomic layer deposition (ALD) can also be used as a method for forming the inorganic layer. The ALD method is a method for forming a thin film in atomic layer units by alternately supplying raw material gases of each element constituting the film to be formed to the surface on which the layer is to be formed.
[0202] (Application) The laminate sheet of the present invention is a laminate sheet that is transparent, has high mechanical strength, and is suppressed from coloring. From the viewpoint of utilizing such excellent optical properties, it is suitable for optical components. For example, it can be used for light-transmitting substrates such as various display devices and various solar cells. In addition, the laminate sheet of the present invention is also suitable for applications such as substrates for electronic devices, components for home appliances, window materials for various vehicles and buildings, interior materials, exterior materials, and packaging materials. EXAMPLES
[0203] The features of the present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below.
[0204] <Production Example 1> [Phosphorylation] As the raw pulp, hardwood dissolving pulp (dry sheet) manufactured by Oji Paper Co., Ltd. was used. This raw pulp was subjected to phosphorylation treatment as follows. First, a mixed aqueous solution of ammonium dihydrogen phosphate and urea was added to 100 parts by mass (bone dry mass) of the raw pulp to adjust the composition to 45 parts by mass of ammonium dihydrogen phosphate, 120 parts by mass of urea, and 150 parts by mass of water, to obtain a chemical-impregnated pulp. Next, the obtained chemical-impregnated pulp was heated for 250 seconds in a hot air dryer at 165°C to introduce phosphoric acid groups into the cellulose in the pulp, to obtain a phosphorylated pulp.
[0205] [Cleaning process] The phosphorylated pulp was then washed. The washing was carried out by pouring 10 L of ion-exchanged water into 100 g (bone dry weight) of phosphorylated pulp to obtain a pulp dispersion, stirring the pulp to uniformly disperse it, and then repeatedly filtering and dehydrating the pulp. The washing was completed when the electrical conductivity of the filtrate reached 100 μS / cm or less.
[0206] [Neutralization process] Next, the phosphorylated pulp after washing was subjected to a neutralization treatment as follows. First, the phosphorylated pulp after washing was diluted with 10 L of ion-exchanged water, and then a 1N aqueous solution of sodium hydroxide was added little by little while stirring to obtain a phosphorylated pulp slurry having a pH of 12 to 13. Next, the phosphorylated pulp slurry was dehydrated to obtain a phosphorylated pulp that had been subjected to a neutralization treatment. Next, the above-mentioned washing treatment was performed on the phosphorylated pulp after the neutralization treatment.
[0207] The infrared absorption spectrum of the phosphorus oxyoxidized pulp obtained in this way was measured using FT-IR. -1 Absorption due to the P=O of the phosphate group was observed near the nucleus, confirming that the phosphate group had been added to the pulp. In addition, when the obtained phosphorylated pulp was analyzed using an X-ray diffractometer, typical peaks were confirmed at two positions, near 2θ=14° to 17° and near 2θ=22° to 23°, confirming that it had cellulose type I crystals.
[0208] [Fiber defibration processing] Ion-exchanged water was added to the obtained phosphorylated pulp to prepare a slurry with a solid content concentration of 2% by mass. This slurry was treated six times with a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a fine fibrous cellulose dispersion liquid containing fine fibrous cellulose. X-ray diffraction confirmed that this fine fibrous cellulose maintained cellulose I type crystals. The amount of phosphoric acid groups (amount of first dissociated acid groups, strong acid groups) measured by the measurement method described in the measurement of [amount of phosphorus oxo acid groups] described later was 1.45 mmol / g. The total amount of dissociated acid was 2.45 mmol / g.
[0209] <Production Example 2> A fine fibrous cellulose dispersion containing phosphorylated pulp and fine fibrous cellulose was obtained in the same manner as in Production Example 1, except that the following nitrogen removal treatment was carried out after the washing treatment and neutralization treatment of the phosphorylated pulp.
[0210] [Nitrogen removal treatment] Ion-exchanged water was added to the phosphorylated pulp to prepare a slurry with a solid content of 4% by mass. A 48% by mass aqueous solution of sodium hydroxide was added to the slurry to adjust the pH to 13.4, and the slurry was heated at a liquid temperature of 85°C for 1 hour. The pulp slurry was then dehydrated, and 10 L of ion-exchanged water was poured into 100 g (bone dry mass) of phosphorylated pulp to obtain a pulp dispersion. The pulp was stirred to disperse uniformly, and the filtration and dehydration were repeated to remove excess sodium hydroxide. The removal was terminated when the electrical conductivity of the filtrate reached 100 μS / cm or less.
[0211] The infrared absorption spectrum of the phosphorus oxyoxidized pulp obtained in this way was measured using FT-IR. -1 Absorption due to the P=O of phosphate groups was observed near the nucleus, confirming that phosphate groups had been added to the pulp. X-ray diffraction also confirmed that the resulting fine fibrous cellulose maintained cellulose type I crystallinity. The amount of phosphate groups (amount of first dissociated acid group, strong acid group) measured by the measurement method described in [Measurement of amount of phosphorus oxo acid group] below was 1.35 mmol / g. The total amount of dissociated acid was 2.30 mmol / g.
[0212] <Production Example 3> [Phosphorus oxide treatment] The same procedure as in Production Example 1 was carried out except that 33 parts by mass of phosphorous acid (phosphonic acid) was used instead of ammonium dihydrogen phosphate in the phosphorylation treatment, to obtain a fine fibrous cellulose dispersion containing phosphorylated pulp and fine fibrous cellulose.
[0213] The infrared absorption spectrum of the phosphorylated pulp obtained was measured using FT-IR. -1Absorption due to P=O of phosphonic acid groups, which are tautomers of phosphorous acid groups, was observed near the nucleus, confirming that phosphorous acid groups (phosphonic acid groups) were added to the pulp. X-ray diffraction also confirmed that the obtained fine fibrous cellulose maintained cellulose type I crystals. The amount of phosphorous acid groups (amount of first dissociated acid) measured by the measurement method described in [Measurement of phosphorus oxoacid group amount] below was 1.51 mmol / g, and the total amount of dissociated acid was 1.54 mmol / g.
[0214] <Production Example 4> [Sulfation treatment] The same procedure as in Production Example 1 was repeated, except that 38 parts by mass of amidosulfuric acid (sulfamic acid) was used instead of ammonium dihydrogen phosphate in the phosphorylation treatment and the heating time was extended to 19 minutes, to obtain a fine fibrous cellulose dispersion containing sulfated pulp and fine fibrous cellulose.
[0215] The infrared absorption spectrum of the sulfated pulp obtained was measured using FT-IR. -1 Absorption due to sulfate groups (sulfonic groups) was observed near the nucleus, confirming that sulfate groups (sulfonic groups) were added to the pulp. In addition, X-ray diffraction confirmed that the obtained fine fibrous cellulose maintained cellulose type I crystals. The amount of sulfonic groups measured by the measurement method described in [Measurement of the amount of sulfonic groups] below was 1.12 mmol / g.
[0216] <Production Example 5> Except for carrying out the following xanthate treatment instead of the phosphorylation treatment, the same operation as in Production Example 1 was carried out to obtain a fine fibrous cellulose dispersion containing xanthate pulp and fine fibrous cellulose.
[0217] [Xanthate treatment] 2500 parts by mass of 8.5% by mass sodium hydroxide aqueous solution was added to 100 parts by mass (bone dry mass) of raw pulp (hardwood dissolving pulp (dry sheet) manufactured by Oji Paper Co., Ltd.), and the mixture was stirred at room temperature for 3 hours to perform an alkali treatment. The pulp after the alkali treatment was centrifuged (filter cloth 400 mesh, 3000 rpm for 5 minutes) to separate the solid and liquid, thereby obtaining a dehydrated alkali cellulose. 3.5 parts by mass of carbon disulfide was added to 10 parts by mass (bone dry mass) of the obtained alkali cellulose, and the sulfurization reaction was carried out at room temperature for 4.5 hours to perform a xanthate treatment.
[0218] X-ray diffraction confirmed that the obtained fine fibrous cellulose maintained cellulose type I crystals. The amount of xanthate groups measured by the measurement method described in [Measurement of the amount of xanthate groups] below was 1.73 mmol / g.
[0219] <Production Example 6> Ion-exchanged water was added to raw pulp (hardwood dissolving pulp (dry sheet) manufactured by Oji Paper Co., Ltd.) to prepare a slurry with a solid content concentration of 2% by mass. This slurry was treated 30 times with a wet pulverizer (Starburst manufactured by Sugino Machine Co., Ltd.) at a pressure of 200 MPa to obtain a cellulose dispersion liquid containing coarse fibrous cellulose.
[0220] [measurement] [Measurement of haze of dispersion liquid] The haze of the dispersion was measured by diluting the fibrous cellulose dispersion with ion-exchanged water to 0.2% by mass, and then measuring with a haze meter (Murakami Color Research Laboratory, HM-150) using a glass cell for liquids with an optical path length of 1 cm (Fujiwara Manufacturing, MG-40, reverse optical path) in accordance with JIS K 7136:2000. The zero point measurement was performed with ion-exchanged water placed in the same glass cell. The dispersion to be measured was left to stand for 24 hours in an environment of 23°C and relative humidity of 50% before measurement. The liquid temperature of the dispersion during measurement was 23°C.
[0221] [Measurement of nanofiber yield] The nanofiber yield after centrifuging the fibrous cellulose dispersion was measured by the method described below. The nanofiber yield is an index of the yield of fine fibrous cellulose, and the higher the nanofiber yield, the higher the yield of fine fibrous cellulose. Each dispersion was adjusted to a cellulose concentration of 0.1% by mass, and centrifuged at 12,000G for 10 minutes using a refrigerated high-speed centrifuge (Kokusan Co., Ltd., H-2000B). The resulting supernatant was collected, and the cellulose concentration of the supernatant was measured. The yield of fine fibrous cellulose was calculated based on the following formula. Nanofiber yield (mass%) = cellulose concentration in supernatant (mass%) / 0.1 × 100
[0222] [Measuring the amount of nitrogen] The total amount of nitrogen contained in the fibrous cellulose and the free nitrogen contained in the fibrous cellulose dispersion was measured by the method described below. Each dispersion was adjusted to a solids concentration of 1 mass% and decomposed by the Kjeldahl method (JIS K 0102:2016 44.1). After decomposition, the amount of ammonium ions (mmol) was measured by cation chromatography and divided by the amount of cellulose (g) used in the measurement to calculate the nitrogen content (mmol / g).
[0223] [Table 1]
[0224] <Example 1> [Substituent removal treatment (high temperature heat treatment)] A 20% by mass aqueous citric acid solution was added to the fine fibrous cellulose dispersion obtained in Production Example 1 to adjust the pH of the dispersion to 5.5. The obtained slurry was placed in a pressure-resistant container and heated at a liquid temperature of 160°C for 15 minutes until the amount of phosphoric acid groups reached 0.08 mmol / g. The formation of fine fibrous cellulose aggregates was confirmed by this operation.
[0225] [Cleaning of slurry after removing substituents] The slurry after heating was washed by repeatedly adding the same amount of ion-exchanged water as the slurry to make a slurry with a solid content concentration of about 1% by mass, stirring the slurry, and then filtering and dehydrating it. When the electrical conductivity of the filtrate became 10 μS / cm or less, ion-exchanged water was added again to make a slurry with a solid content of about 1% by mass, and the slurry was left to stand for 24 hours. From there, the operation of filtering and dehydrating was further repeated, and the point when the electrical conductivity of the filtrate became 10 μS / cm or less again was determined as the end point of washing. Ion-exchanged water was added to the obtained fine fibrous cellulose aggregates, and a slurry was obtained after removing the substituents. The solid content concentration of this slurry was 1.7% by mass.
[0226] [Uniform dispersion of slurry after removing substituents] Ion-exchanged water was added to the obtained slurry after the removal of the substituents to obtain a slurry with a solid content concentration of 1.0% by mass. The pH of this slurry was 5.5. The slurry was treated three times at a pressure of 200 MPa using a wet pulverizer (Starburst, manufactured by Sugino Machine Co., Ltd.) to obtain a dispersion of the substituent-removed fine fibrous cellulose containing the substituent-removed fine fibrous cellulose. The number-average fiber width of the substituent-removed fine fibrous cellulose measured in [Measurement of fiber width] described later was 4 nm, and the proportion of fiber widths of 10 nm or less was 98%.
[0227] [Preparation of sheet 1] Acetoacetyl-modified polyvinyl alcohol (Gosenex Z-200, manufactured by Mitsubishi Chemical Corporation) was added to ion-exchanged water to a concentration of 12% by mass, and dissolved by stirring at 95° C. for 1 hour. By the above procedure, an aqueous polyvinyl alcohol solution was obtained.
[0228] The substituent-removed fine fibrous cellulose dispersion and the polyvinyl alcohol aqueous solution were each diluted with ion-exchanged water to a solid content concentration of 0.6% by mass. Then, 70 parts by mass of the diluted substituent-removed fine fibrous cellulose dispersion were mixed with 30 parts by mass of the diluted polyvinyl alcohol aqueous solution to obtain a mixed solution. Furthermore, the finished basis weight of the sheet was 37.5 g / m 2The mixed solution was weighed out so that the mixture had a surface area of 100 mm and was spread on a commercially available acrylic plate. A damming frame (inner dimensions 250 mm x 250 mm, height 5 cm) was placed on the acrylic plate so that the desired basis weight was obtained. The mixture was then dried in a dryer at 70°C for 24 hours and peeled off from the acrylic plate to obtain a sheet containing fine fibrous cellulose from which the substituent groups had been removed. The thickness of the sheet was 25 μm. The surface pH of the sheet containing fine fibrous cellulose from which the substituent groups had been removed before the resin layer was laminated was 4.8.
[0229] [Formation of resin layer] A resin composition was obtained by mixing 100 parts by mass of an acrylic resin (manufactured by Taisei Fine Chemical Co., Ltd., Acrylit 8KX-012C, solid content concentration 39% by mass) in which an acryloyl group having a hydroxyl group was graft-polymerized, 38 parts by mass of a polyisocyanate compound (manufactured by Asahi Kasei Chemicals Corporation, TPA-100), and 100 parts by mass of methyl ethyl ketone. Next, the resin composition was applied to one side of the sheet containing the substituent-removed fine fibrous cellulose with a bar coater, and then heated at 100°C for 1 hour to harden the sheet, thereby laminating a resin layer. Furthermore, a resin layer was laminated on the other side of the sheet containing the substituent-removed fine fibrous cellulose in the same manner. The thickness of the resin layer was 5 μm per side. By the above procedure, a laminate sheet was obtained in which a resin layer was laminated on both sides of the sheet containing the substituent-removed fine fibrous cellulose.
[0230] <Example 2> A laminated sheet was obtained in the same manner as in Example 1, except that the substituent removal treatment was carried out for 5 days at a liquid temperature of 85° C. The surface pH of the substituent-removed fine fibrous cellulose-containing sheet before laminating the resin layer was 4.7.
[0231] <Example 3> The fine fibrous cellulose dispersion obtained in Production Example 1 was diluted to 0.7% by mass, subjected to a substituent removal treatment, and after the washing treatment step following the substituent removal, ion-exchanged water was added to the obtained fine fibrous cellulose aggregate to prepare a slurry having a solid content concentration of 1.0% by mass, and a laminated sheet was obtained in the same manner as in Example 1. The surface pH of the sheet containing the substituent-removed fine fibrous cellulose before laminating the resin layer was 4.8.
[0232] <Example 4> A laminate sheet was obtained in the same manner as in Example 1, except that the substituent removal treatment was carried out at a liquid temperature of 160° C. for 40 minutes until the amount of phosphoric acid groups reached 0.05 mmol / g. The surface pH of the substituent-removed fine fibrous cellulose-containing sheet before laminating the resin layer was 4.8.
[0233] <Example 5> A laminated sheet was obtained in the same manner as in Example 1, except that the substituent removal treatment was carried out at a liquid temperature of 150° C. for 15 minutes until the amount of phosphoric acid groups reached about 0.21 mmol / g. The surface pH of the substituent-removed fine fibrous cellulose-containing sheet before laminating the resin layer was 4.9.
[0234] <Example 6> A laminate sheet was obtained in the same manner as in Example 1, except that the substituent removal treatment was carried out at a liquid temperature of 140° C. for 20 minutes until the amount of phosphoric acid groups reached about 0.40 mmol / g. The surface pH of the substituent-removed fine fibrous cellulose-containing sheet before laminating the resin layer was 4.7.
[0235] <Example 7> A laminated sheet was obtained in the same manner as in Example 1, except that the pH of the fine fibrous cellulose dispersion liquid to be subjected to the substituent removal treatment was adjusted to 2.4, and the pH of the slurry after the substituent removal washing treatment was adjusted to 5.5. The amount of phosphoric acid groups after the substitution removal was 0.22 mmol / g. The surface pH of the substitution-removed fine fibrous cellulose-containing sheet before laminating the resin layer was 4.7.
[0236] <Example 8> A laminated sheet was obtained in the same manner as in Example 1, except that the pH of the fine fibrous cellulose dispersion liquid to be subjected to the substituent removal treatment was not adjusted, but was heated, and the pH of the slurry after the substituent removal was adjusted to 5.5 after the washing treatment. The amount of phosphoric acid groups after the substitution removal was 0.29 mmol / g. The surface pH of the substitution-removed fine fibrous cellulose-containing sheet before laminating the resin layer was 4.9.
[0237] <Example 9> A laminated sheet was obtained in the same manner as in Example 1, except that the slurry after the removal of the substituents was uniformly dispersed using a high-speed defibrator (Clearmix-11S, manufactured by M Technique Co., Ltd.) at a peripheral speed of 34 m / sec for 180 minutes. The surface pH of the sheet containing the fine fibrous cellulose after the removal of the substituents before laminating the resin layer was 4.8.
[0238] <Example 10> A laminated sheet was obtained in the same manner as in Example 1, except that the substituent removal treatment was carried out by the following enzyme treatment instead of a heat treatment, and further, the slurry after the substituent removal was washed by the following method. The surface pH of the substituent-removed fine fibrous cellulose-containing sheet before laminating the resin layer was 4.8.
[0239] [Substituent removal treatment (enzyme treatment)] A 20% by mass aqueous citric acid solution was added to the obtained fine fibrous cellulose dispersion, and the slurry was adjusted to pH 5.5. Acid phosphatase (Sumiteam PM manufactured by Shin Nippon Chemical Industry Co., Ltd.) was added to the obtained slurry in an amount of 3 parts by mass per 100 parts by mass of fine fibrous cellulose, and the enzyme treatment was carried out for 2.5 hours in a water bath at 37°C. The production of fine fibrous cellulose aggregates was confirmed by this operation.
[0240] [Cleaning treatment of slurry after removal of substituents by enzyme treatment] To the obtained slurry after removing the substituents, a strongly basic ion exchange resin (Amberjet 4400; Organo Corporation, conditioned) and a weakly acidic ion exchange resin (Amberlite IRC76; Organo Corporation, conditioned) in an amount of 1 / 5 by volume were added, and the mixture was shaken for 1 hour. The slurry was then washed by pouring it onto a mesh with 90 μm openings to separate the resin and the slurry.
[0241] <Example 11> A laminate sheet was obtained in the same manner as in Example 1, except that the fine fibrous cellulose dispersion obtained in Production Example 2 was used instead of the fine fibrous cellulose dispersion obtained in Production Example 1. The surface pH of the substituent-removed fine fibrous cellulose-containing sheet before laminating the resin layer was 4.7.
[0242] <Example 12> A laminate sheet was obtained in the same manner as in Example 1, except that the fine fibrous cellulose dispersion obtained in Production Example 3 was used instead of the fine fibrous cellulose dispersion obtained in Production Example 1. The surface pH of the substituent-removed fine fibrous cellulose-containing sheet before laminating the resin layer was 4.7.
[0243] <Example 13> A laminate sheet was obtained in the same manner as in Example 1, except that the fine fibrous cellulose dispersion obtained in Production Example 4 was used instead of the fine fibrous cellulose dispersion obtained in Production Example 1. The surface pH of the substituent-removed fine fibrous cellulose-containing sheet before laminating the resin layer was 4.8.
[0244] <Example 14> Instead of the fine fibrous cellulose dispersion obtained in Production Example 1, the fine fibrous cellulose dispersion obtained in Production Example 5 was used. Furthermore, instead of the substituent removal treatment (high temperature heat treatment), a substituent removal treatment (low temperature heat treatment) described below was performed. Otherwise, a laminated sheet was obtained in the same manner as in Example 1. The surface pH of the sheet containing the substituent-removed fine fibrous cellulose before laminating the resin layer was 6.9.
[0245] [Removal of substituents (low-temperature heat treatment)] The obtained fine fibrous cellulose dispersion was heated at a liquid temperature of 40°C for 45 minutes until the amount of xanthate groups became less than 0.08 mmol / g.
[0246] <Example 15> In the [Formation of Resin Layer], except that a resin layer was formed only on one side of the sheet containing substituent-removed fine fibrous cellulose, a laminated sheet was obtained in the same manner as in Example 1. The surface pH of the sheet containing substituent-removed fine fibrous cellulose before laminating the resin layer was 4.8.
[0247] <Example 16> In [Sheet Preparation 1], instead of the polyvinyl alcohol aqueous solution having a solid content concentration of 0.6 mass%, polyethylene oxide (Sumitomo Seika Chemicals, PEO-18; viscosity average molecular weight 4.3 million to 4.8 million) diluted to a solid content concentration of 0.6 mass% was used. The rest was the same as in Example 1 to obtain a laminated sheet. The surface pH of the substituent-removed fine fibrous cellulose-containing sheet before laminating the resin layer was 4.8.
[0248] <Example 17> A laminated sheet was obtained in the same manner as in Example 1, except that the procedure of [Formation of resin layer] was changed as follows. 15 parts by mass of modified polycarbonate resin (manufactured by Mitsubishi Gas Chemical Company, Inc., Iupizeta FPC-2136), 57 parts by mass of toluene, and 28 parts by mass of methyl ethyl ketone were mixed to obtain a resin coating liquid. Next, 2.25 parts by mass of an isocyanate compound (manufactured by Asahi Kasei Chemicals Corporation, Duranate TPA-100) was added as an adhesion aid to the resin coating liquid, and mixed to obtain a resin composition. Next, the resin composition was applied to one side of the substituent-removed fine fibrous cellulose-containing sheet with a bar coater, and then heated at 100°C for 1 hour to harden the resin layer. Furthermore, a resin layer was laminated on the other side of the substituent-removed fine fibrous cellulose-containing sheet in the same manner. The thickness of the resin layer was 5 μm per side. The surface pH of the substituent-removed fine fibrous cellulose-containing sheet before laminating the resin layer was 4.8.
[0249] <Example 18> In [Preparation of Sheet 1], 40 parts by mass of the diluted dispersion of the substituent-removed fine fibrous cellulose was mixed with 60 parts by mass of the diluted aqueous polyvinyl alcohol solution to obtain a mixed liquid. Furthermore, the finished basis weight of the sheet was 35.0 g / m2 The mixture was measured so that the mixture was 0.01g / ml and spread on a commercially available acrylic plate. The rest of the procedure was the same as in Example 17 to obtain a laminated sheet. The thickness of the sheet containing the substituent-removed fine fibrous cellulose was 25 μm. The surface pH of the sheet containing the substituent-removed fine fibrous cellulose before laminating the resin layer was 3.2.
[0250] <Example 19> In [Preparation of Sheet 1], 10 parts by mass of the diluted dispersion of the removed substituent-containing fine fibrous cellulose was mixed with 90 parts by mass of the diluted aqueous polyvinyl alcohol solution to obtain a mixed solution. Furthermore, the finished basis weight of the sheet was 31.0 g / m 2 The mixture was measured so that the thickness of the mixture was 100 μm, and the mixture was spread on a commercially available acrylic plate. The rest of the procedure was the same as in Example 17 to obtain a laminated sheet. The thickness of the sheet containing the substituent-removed fine fibrous cellulose was 25 μm. The surface pH of the sheet containing the substituent-removed fine fibrous cellulose before laminating the resin layer was 3.0.
[0251] <Example 20> In [Sheet Production 1], the finished sheet has a basis weight of 105.0 g / m 2 A laminated sheet was obtained in the same manner as in Example 17, except that the mixed solution was measured so that the thickness of the mixed solution was 70 μm, and the mixed solution was spread on a commercially available acrylic plate. The thickness of the sheet containing the substituent-removed fine fibrous cellulose was 70 μm. The surface pH of the sheet containing the substituent-removed fine fibrous cellulose before laminating the resin layer was 4.8.
[0252] <Example 21> A laminated sheet was obtained in the same manner as in Example 20, except that the procedure of [Formation of Resin Layer] was changed as follows. 15 parts by mass of modified polycarbonate resin (manufactured by Mitsubishi Gas Chemical Company, Iupizeta FPC-2136), 57 parts by mass of toluene, and 28 parts by mass of methyl ethyl ketone were mixed to obtain a resin coating liquid. Next, 0.75 parts by mass of methacryloxypropyltrimethoxysilane (manufactured by Momentive Performance Materials Japan, SILQUEST A-174 SILANE), which is an organosilicon compound (silane coupling agent) as an adhesion aid, was added to the resin coating liquid and mixed to obtain a resin composition. Next, the resin composition was applied to one side of the sheet containing the substituent-removed fine fibrous cellulose with a bar coater, and then heated at 100°C for 1 hour to harden the resin layer. Furthermore, a resin layer was laminated on the other side of the sheet containing the substituent-removed fine fibrous cellulose in the same manner. The thickness of the resin layer was 5 μm per side. The surface pH of the sheet containing the substituent-removed fine fibrous cellulose before laminating the resin layer was 4.8.
[0253] <Comparative Example 1> A fine fibrous cellulose-containing sheet was obtained by carrying out the same operation as in the above [Sheet Preparation 1], except that the fine fibrous cellulose dispersion obtained in Production Example 1 was used instead of the substituent-removed fine fibrous cellulose dispersion in [Sheet Preparation 1]. The surface pH of the fine fibrous cellulose-containing sheet before laminating the resin layer was 7.3.
[0254] <Comparative Example 2> A fine fibrous cellulose-containing sheet was obtained in the same manner as in Comparative Example 1, except for using the fine fibrous cellulose dispersion obtained in Production Example 3. The surface pH of the fine fibrous cellulose-containing sheet before laminating the resin layer was 7.2.
[0255] <Comparative Example 3> A fine fibrous cellulose-containing sheet was obtained in the same manner as in Comparative Example 1, except that the fine fibrous cellulose dispersion obtained in Production Example 4 was used. The surface pH of the fine fibrous cellulose-containing sheet before laminating the resin layer was 6.9.
[0256] <Comparative Example 4> A fine fibrous cellulose-containing sheet was obtained in the same manner as in Comparative Example 1, except that the fine fibrous cellulose dispersion obtained in Production Example 5 was used. The surface pH of the fine fibrous cellulose-containing sheet before laminating the resin layer was 6.3.
[0257] <Comparative Example 5> A laminate sheet was obtained in the same manner as in Example 1, except that the substituent removal treatment was carried out at a liquid temperature of 140° C. for 10 minutes until the amount of phosphoric acid groups reached about 0.74 mmol / g. The surface pH of the substituent-removed fine fibrous cellulose-containing sheet before laminating the resin layer was 4.9.
[0258] <Comparative Example 6> A laminated sheet was obtained in the same manner as in Comparative Example 1, except for using the cellulose dispersion containing the coarse fibrous cellulose obtained in Production Example 6. The surface pH of the coarse fibrous cellulose-containing sheet before laminating the resin layer was 5.8.
[0259] <Comparative Example 7> Except for not uniformly dispersing the slurry after the removal of the substituents, a laminated sheet was obtained in the same manner as in Example 1. The surface pH of the sheet containing the fibrous cellulose from which the substituents had been removed before laminating the resin layer was 4.8.
[0260] <Comparative Example 8> Except for not uniformly dispersing the slurry after the removal of the substituents, a laminated sheet was obtained in the same manner as in Example 12. The surface pH of the sheet containing the fibrous cellulose from which the substituents had been removed before laminating the resin layer was 4.6.
[0261] <Comparative Example 9> Except for not uniformly dispersing the slurry after the removal of the substituents, a laminated sheet was obtained in the same manner as in Example 13. The surface pH of the sheet containing the fibrous cellulose from which the substituents had been removed before laminating the resin layer was 4.5.
[0262] <Comparative Example 10> Except for not uniformly dispersing the slurry after the removal of the substituents, a laminated sheet was obtained in the same manner as in Example 14. The surface pH of the sheet containing the fibrous cellulose from which the substituents had been removed before laminating the resin layer was 6.8.
[0263] <Comparative Example 11> A laminated sheet was obtained in the same manner as in Example 15, except that in [Sheet Preparation 1], the fine fibrous cellulose dispersion obtained in Production Example 1 was used instead of the substituent-removed fine fibrous cellulose dispersion. The surface pH of the fine fibrous cellulose-containing sheet before laminating the resin layer was 7.3.
[0264] <Comparative Example 12> A laminated sheet was obtained in the same manner as in Example 16, except that in [Sheet Preparation 1], the fine fibrous cellulose dispersion obtained in Production Example 1 was used instead of the substituent-removed fine fibrous cellulose dispersion. The surface pH of the fine fibrous cellulose-containing sheet before laminating the resin layer was 7.2.
[0265] <Comparative Example 13> A laminated sheet was obtained in the same manner as in Example 17, except that in [Sheet Preparation 1], the fine fibrous cellulose dispersion obtained in Production Example 1 was used instead of the substituent-removed fine fibrous cellulose dispersion. The surface pH of the fine fibrous cellulose-containing sheet before laminating the resin layer was 7.3.
[0266] <Comparative Example 14> A laminated sheet was obtained in the same manner as in Example 18, except that in [Sheet Preparation 1], the fine fibrous cellulose dispersion obtained in Production Example 1 was used instead of the substituent-removed fine fibrous cellulose dispersion. The surface pH of the fine fibrous cellulose-containing sheet before laminating the resin layer was 6.9.
[0267] <Comparative Example 15> A laminated sheet was obtained in the same manner as in Example 20, except that in [Sheet Preparation 1], the fine fibrous cellulose dispersion obtained in Production Example 1 was used instead of the substituent-removed fine fibrous cellulose dispersion. The surface pH of the fine fibrous cellulose-containing sheet before laminating the resin layer was 7.2.
[0268] <Comparative Example 16> A laminated sheet was obtained in the same manner as in Example 21, except that in [Sheet Preparation 1], the fine fibrous cellulose dispersion obtained in Production Example 1 was used instead of the substituent-removed fine fibrous cellulose dispersion. The surface pH of the fine fibrous cellulose-containing sheet before laminating the resin layer was 7.2.
[0269] <Comparative Example 17> A laminated sheet was obtained in the same manner as in Example 1, except that the following [Ion exchange resin treatment of the slurry after the removal of substituents] was carried out instead of the [Washing treatment of the slurry after the removal of substituents]. The surface pH of the sheet containing the substituent-removed fine fibrous cellulose before laminating the resin layer was 2.4.
[0270] [Ion exchange resin treatment of slurry after removal of substituents] Ion exchange water was added to the slurry obtained after heating in the [Substituent removal treatment (high temperature heat treatment)] to make a slurry with a solid content concentration of about 1.1 mass%, and then a strongly acidic ion exchange resin (Amberjet 1024; Organo Corporation, conditioned) was added at a volume ratio of 1 / 10 and a strongly basic ion exchange resin (Amberjet 4400; Organo Corporation, conditioned) was added at a volume ratio of 1 / 10, and the mixture was shaken for 1 hour, after which the resin and the slurry were separated by pouring onto a mesh with 90 μm openings. The resulting slurry had a pH of 3.1.
[0271] <Comparative Example 18> A laminated sheet was obtained in the same manner as in Comparative Example 17, except that in the [substituent removal treatment (high temperature heat treatment)], citric acid was not added, and urea was added in an amount 1 / 10 of the fine fibrous cellulose dispersion liquid. The surface pH of the substituent-removed fine fibrous cellulose-containing sheet before laminating the resin layer was 2.4.
[0272] [evaluation] The laminate sheets obtained in the examples and comparative examples were evaluated by the following methods.
[0273] [Fiber width measurement] The fiber width of the fibrous cellulose was measured by the following method. Each fibrous cellulose dispersion was diluted with water so that the cellulose concentration was 0.01% by mass or more and 0.1% by mass or less, and cast on a hydrophilized carbon film-coated grid. After drying, it was stained with uranyl acetate and observed with a transmission electron microscope (TEM, manufactured by JEOL-2000EX, manufactured by JEOL Co., Ltd.). At that time, an axis of arbitrary image width in the vertical and horizontal directions was assumed in the obtained image, and the magnification was adjusted so that 20 or more fibers crossed the axis. After obtaining an observation image satisfying this condition, two random axes were drawn vertically and horizontally on this image, and the fiber width of the fibers crossing the axis was read visually. Three non-overlapping observation images were taken for each dispersion, and the fiber width value of the fibers crossing the two axes was read (20 or more × 2 × 3 = 120 or more). The number average fiber width was calculated from the fiber width obtained in this way. However, the measurements were performed using a substituent-removed fine fibrous cellulose dispersion in Examples 1 to 21 and Comparative Examples 5, 7 to 10, and a fine fibrous cellulose dispersion in Comparative Examples 1 to 4 and 11 to 16. For the coarse fibrous cellulose used in Comparative Example 6 alone, the dispersion was diluted with water so that the cellulose concentration was 0.01% by mass or more and 0.1% by mass or less, and then cast onto a glass plate and observed with a scanning electron microscope (SEM). In addition, the proportion of fine fibrous cellulose having a fiber width of 10 nm or less was calculated based on the following formula. Percentage of fine fibrous cellulose with a fiber width of 10 nm or less (%) = (number of fine fibrous cellulose with a fiber width of 10 nm or less / total number of fibrous cellulose) x 100
[0274] [Measurement of phosphorus oxoacid group content] In measuring the amount of phosphorus oxoacid groups (amount of phosphate groups or phosphite groups), ion-exchanged water was first added to the target fine fibrous cellulose to prepare a slurry with a solid content of 0.2% by mass. The obtained slurry was treated with an ion-exchange resin, and then titrated with an alkali to measure the amount of phosphorus oxoacid groups. Treatment with ion exchange resin was carried out by adding 1 / 10 by volume of a strongly acidic ion exchange resin (Amberjet 1024; Organo Corporation, conditioned) to the above-mentioned fine fibrous cellulose-containing slurry, shaking for 1 hour, and then pouring onto a mesh with 90 μm openings to separate the resin and the slurry. The titration using alkali was performed by adding 10 μL of 0.1N sodium hydroxide solution to the slurry containing fine fibrous cellulose after the treatment with ion exchange resin every 5 seconds, while measuring the change in the pH value of the slurry. The titration was performed while blowing nitrogen gas into the slurry 15 minutes before the start of the titration. In this neutralization titration, two points were observed where the increment (the differential value of pH with respect to the amount of alkali added) was maximum on the curve plotting the measured pH against the amount of alkali added. Of these, the first maximum point of the increment obtained after the start of the addition of alkali is called the first end point, and the second maximum point of the increment obtained next is called the second end point (Figure 2). The amount of alkali required from the start of the titration to the first end point is equal to the amount of first dissociated acid in the slurry used for the titration. The amount of alkali required from the start of the titration to the second end point is equal to the total amount of dissociated acid in the slurry used for the titration. The amount of alkali (mmol) required from the start of titration to the first end point was divided by the solid content (g) in the slurry to be titrated, and this value was taken as the amount of phosphorus oxoacid groups (mmol / g).
[0275] [Measurement of sulfonic acid group content] The amount of sulfonic groups was measured as follows. The fine fibrous cellulose was frozen in a freezer and then dried for 3 days in a freeze dryer (FreeZone, manufactured by Labconco). The freeze-dried product was pulverized into powder form using a hand mixer (Labo Millser PLUS, manufactured by Osaka Chemical) at a rotation speed of 20,000 rpm for 60 seconds. The freeze-dried and pulverized sample was subjected to pressurized heat decomposition using nitric acid in a closed container. The sample was then appropriately diluted and the amount of sulfur was measured by ICP-OES. The value calculated by dividing by the bone dry mass of the fine fibrous cellulose used was taken as the amount of sulfate ester groups (unit: mmol / g).
[0276] [Measurement of xanthate group content] The amount of xanthate groups was measured by the Bredee method. Specifically, 40 mL of saturated ammonium chloride solution was added to 1.5 parts by mass (absolute dry mass) of fibrous cellulose, the sample was crushed with a glass rod and mixed well, and after leaving it for about 15 minutes, it was filtered with GFP filter paper (GS-25 manufactured by ADVANTEC) and thoroughly washed with saturated ammonium chloride solution. The sample was placed in a 500 mL tall beaker together with the GFP filter paper, and 50 mL of 0.5 M sodium hydroxide solution (5 ° C.) was added and stirred. After leaving it for 15 minutes, a phenolphthalein solution was added until the solution turned pink, and then 1.5 M acetic acid was added, and the point at which the solution changed from pink to colorless was taken as the neutralization point. After neutralization, 250 mL of distilled water was added and stirred well, and 10 mL of 1.5 M acetic acid and 10 mL of 0.05 mol / L iodine solution were added using a whole pipette. This solution was titrated with 0.05 mol / L sodium thiosulfate solution. The amount of xanthate groups was calculated from the titration amount of sodium thiosulfate and the bone dry mass of fibrous cellulose using the following formula. Amount of xanthate group (mmol / g) = (0.05 x 10 x 2 - 0.05 x sodium thiosulfate titration (mL)) / 1000 / bone dry mass of fibrous cellulose (g)
[0277] [Measurement of total light transmittance of laminated sheet] The total light transmittance of the laminated sheet was measured using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory) in accordance with JIS K 7361-1:1997.
[0278] [Haze measurement of laminated sheets] The haze of the laminated sheet was measured using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory) in accordance with JIS K 7136:2000.
[0279] [Yellowness measurement of laminated sheet before and after heating] The yellowness index (YI value) of the laminated sheet before and after heating was measured using Colour Cute i (manufactured by Suga Test Instruments Co., Ltd.) in accordance with JIS K 7373:2006. The YI value after heating was the YI value of the laminated sheet heated at 160°C for 6 hours. The YI increase rate was measured by the following method. YI increase rate (%) = (YI value of sheet after heating - YI value of sheet before heating) / YI value of sheet before heating × 100
[0280] [Measurement of surface pH of sheet (CNF sheet) before laminating resin layer] 10 μL of ion-exchanged water was dropped onto a 1 cm square area on the surface of the sheet using a micropipette, and the pH of that area was measured using a flat pH composite electrode (6261-10C; manufactured by HORIBA).
[0281] [Table 2]
[0282] [Table 3]
[0283] [Table 4]
[0284] [Table 5]
[0285] AC: Acrylic PIC: Polyisocyanate PC: Polycarbonate OSi: Organosilane
[0286] The laminate sheets obtained in the examples were highly transparent, and the YI before heating as well as the YI after heating were low (Examples 1 to 21). On the other hand, when the treatment for removing the substituents was not performed or was insufficient, the obtained laminate sheets had high YI after heating (Comparative Examples 1 to 5, 11 to 16). When unmodified coarse fibrous cellulose was used, the obtained laminate sheets were opaque (Comparative Example 6). When uniform dispersion after removal of the substituents was not performed, the transparency of the laminate sheets was low (Comparative Examples 7 to 10).
[0287] <Example 101> Two sheets of the laminated sheet obtained in Example 20 were prepared by trimming to 100 mm square. A polycarbonate plate having dimensions of 100 mm square and thickness of 2 mm was sandwiched between two of these laminated sheets, and these were further sandwiched between two stainless steel plates having dimensions of 200 mm square. After that, it was inserted into a mini test press (manufactured by Toyo Seiki Kogyo Co., Ltd., MP-WCH) set at room temperature and heated to 160 ° C. over 3 minutes under a press pressure of 0.2 MPa. After holding in this state for 30 seconds, it was cooled to 30 ° C. over 3 minutes. By the above procedure, a laminate with a polycarbonate plate was obtained.
[0288] <Example 102> A laminate with a polycarbonate plate was obtained in the same manner as in Example 101, except that the laminate sheet obtained in Example 21 was used.
[0289] <Comparative Example 101> A laminate with a polycarbonate plate was obtained in the same manner as in Example 101, except that the laminate sheet obtained in Comparative Example 15 was used.
[0290] <Comparative Example 102> A laminate with a polycarbonate plate was obtained in the same manner as in Example 101, except that the laminate sheet obtained in Comparative Example 16 was used.
[0291] <Comparative Example 103> In Example 101, the polycarbonate plate was not sandwiched between the two laminated sheets, but was treated with the mini test press. This plate was used for evaluation.
[0292] [evaluation] The laminates and plates obtained in the examples and comparative examples were evaluated by the following methods.
[0293] [Measurement of bending elastic modulus] Test pieces measuring 80 mm x 10 mm were cut out from the laminate and plate, and a bending test was performed according to JIS K 7171:2016 to measure the bending modulus.
[0294] [exterior] The YI values of the laminates and plates were measured in accordance with JIS K 7373:2006 using Colour Cute i (manufactured by Suga Test Instruments Co., Ltd.) From the measurement results, the appearance was evaluated according to the following criteria. A: YI is less than 10 B: YI is 10 or more
[0295] [exterior] The laminate and the plate were heated at 90° C. for 720 hours. Thereafter, the YI values of the laminate and the plate were measured using Colour Cute i (manufactured by Suga Test Instruments Co., Ltd.) in accordance with JIS K 7373:2006. From the measurement results, the appearance was evaluated according to the following criteria. A: YI is less than 15 B: YI is 15 or more
[0296] [Table 6]
[0297] The laminated sheets obtained in the examples had low YI before and after heating and good appearance. Furthermore, when made into a laminate, the flexural modulus was high and the reinforcing effect of the resin material was excellent (Examples 101 and 102). The laminated sheets that did not undergo the process including the substituent removal treatment had a slightly low flexural modulus and poor appearance when made into a laminate (Comparative Examples 101 and 102). [Explanation of symbols]
[0298] 2 Resin layer 6 Fiber Layer 10 Laminated sheet
Claims
1. A laminated sheet having a fiber layer and a resin layer disposed on at least one surface of the fiber layer, The fiber layer comprises a fibrous cellulose having an introduced substituent amount of less than 0.5 mmol / g and a fiber width of 1 to 10 nm.
2. The laminate sheet according to claim 1 , wherein the substituent is an anionic group.
3. The laminate sheet according to claim 2 , wherein the anionic group is a phosphorus oxoacid group or a functional group derived from a phosphorus oxoacid group.
4. The laminated sheet according to any one of claims 1 to 3, wherein the fibrous cellulose has a carbamide group.
5. The laminate sheet according to any one of claims 1 to 4, wherein the fiber layer has a thickness of 20 µm or more.
6. The density of the fiber layer is 1.0 g / cm 3 The laminate sheet according to any one of claims 1 to 5.
7. The laminate sheet according to any one of claims 1 to 6, wherein the resin layer is directly laminated to the fiber layer.
8. The laminate sheet according to any one of claims 1 to 7, wherein the resin layer contains at least one resin selected from a polycarbonate resin and an acrylic resin.
9. The laminate sheet according to any one of claims 1 to 8, wherein the resin layer further comprises an adhesion assistant.
10. The laminate sheet according to claim 9 , wherein the adhesion assistant is at least one selected from an isocyanate compound and an organosilicon compound.
11. The laminate sheet according to claim 9 or 10, wherein the adhesion assistant is an isocyanate compound, and the content of the isocyanate compound is 10 parts by mass or more and 40 parts by mass or less relative to 100 parts by mass of the resin contained in the resin layer.
12. The laminate sheet according to any one of claims 1 to 11, having a YI value of 2.0 or less.
13. The laminate sheet according to any one of claims 1 to 12, having a haze of 2.0% or less.
14. The laminate sheet according to any one of claims 1 to 13, which is for use as an optical member.
15. A laminate comprising the laminate sheet according to any one of claims 1 to 14 and an adherend.
Citation Information
Patent Citations
Moisture-resistant composite sheet that comprises base sheet layer comprising fine fiber and inorganic layer
JP2016037031A
Gas barrier laminate
JP2017136814A
Method for manufacturing fine fiber and fine-fiber-containing sheet, sheet obtained using said method, and resin complex in which resin is layered
WO2015182438A1
Laminate and method for producing laminate
WO2017126432A1
Laminate and method for producing the same
JP2014079938A